Organic electrode light emitting device and display device including same
By using light-transmitting electrodes combining metal oxide transparent conductive film layers in bottom luminescent OLED devices, the photoelectric efficiency and stability problems of traditional OLED devices are solved, and the effects of high current efficiency, good color purity and long service life are achieved.
Patent Information
- Application Number
- CN202410903196.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-06
- Filing Date
- 2024-07-05
- Publication Date
- 2025-01-07
AI Technical Summary
In traditional bottom luminescent OLED devices, the anode usually uses a single transparent metal oxide conductive film, resulting in uneven light intensity distribution, poor photoelectric efficiency, and unstable device, making it difficult to achieve high current efficiency, good color purity and long service life.
A light-transmitting electrode consisting of a first metal oxide transparent conductive film layer, a metal film layer and a second metal oxide transparent conductive film layer is used to combine a specific metal such as Ag, Al, Cu, Ca, Cr, Mg, Zn or Mo, improves conductive performance and stability, and improves the microcavity effect through film thickness optimization.
It realizes high current efficiency, good color purity and stability of OLED devices, reduces production costs, improves the cost-effectiveness of the device, and significantly improves the service life.
Smart Images

Figure CN119277893A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of semiconductor technology, and more specifically, to a bottom-emitting organic electroluminescent (OLED) device, which includes a light-transmitting electrode, wherein the light-transmitting electrode includes a first metal oxide transparent conductive film layer, a metal film layer, and a second metal oxide transparent conductive film layer; the present invention also relates to a display device including the OLED device. The OLED device and the display device have improved current efficiency and color purity. Background Art
[0002] Organic light emitting diodes (OLED) device technology can be used to manufacture new display products and new lighting products, and is expected to replace existing liquid crystal displays and fluorescent lighting, with a wide range of applications. With the expansion of the application field of OLED technology, people have put forward higher requirements for the photoelectric efficiency, color rendering performance and service life of OLED devices.
[0003] At present, in traditional bottom-emitting OLED devices, the anode usually uses a single transparent metal oxide conductive film, which is often accompanied by uneven light intensity distribution, poor photoelectric efficiency, etc. In this regard, the improvement method includes: using a single Ag film as the anode, but since the single Ag metal will agglomerate or partially crystallize, the device will be unstable, and safety problems such as leakage or short circuit will occur, and the resistance will increase and the device structure will be unstable.
[0004] The micro-resonance cavity effect refers to the optical interference effect inside the OLED device. The luminous characteristics of the micro-resonance cavity can be determined by the optical length of the micro-resonance cavity, and are related to the thickness and refractive index of each layer of material. Generally, an optical length control layer of different thicknesses needs to be added to adjust it. The optical length control layer is generally called an optical modulation layer. For common bottom-emitting devices, the existing technology is generally divided into strong micro-cavities and weak micro-cavities. Strong micro-cavities refer to the situation that when the reflectivity of the cathode and the anode is relatively high, the micro-cavity has a more significant effect on the enhancement of a specific wavelength, and the half-width is very narrow; on the contrary, weak micro-cavities refer to the situation that when the reflectivity of the cathode and the anode is relatively low, the micro-cavity has a less obvious effect on the enhancement of a specific wavelength, and the half-width is relatively wide. Top-emitting OLED devices belong to strong micro-cavities, which are mainly achieved by adjusting the organic functional material layer, with high implementation difficulty and complex process. Bottom-emitting OLED devices belong to weak micro-cavities, so the device efficiency is low and the color purity is poor.
[0005] Therefore, it is of great significance to provide a bottom-emitting OLED device with higher current efficiency, good color purity and service life, and strong microcavity characteristics. Summary of the invention
[0006] An object of the present invention is to provide an organic electroluminescent device having improved current efficiency, color purity and service life.
[0007] In a first aspect of the present invention, an organic electroluminescent device is provided, which comprises, from bottom to top, a substrate, a light-transmitting electrode, an organic functional material layer, and a reflective electrode, wherein the light-transmitting electrode comprises: a first metal oxide transparent conductive film layer, which directly covers the substrate; a metal film layer, which directly covers the first metal oxide transparent conductive film layer; and a second metal oxide transparent conductive film layer, which directly covers the metal film layer.
[0008] A second aspect of the present invention provides a display device including the structural features of the organic electroluminescent device of the first aspect.
[0009] Beneficial technical effects
[0010] The present invention achieves the following technical effects by arranging a light-transmitting electrode including a first metal oxide transparent conductive film layer, a metal film layer and a second metal oxide transparent conductive film layer on a substrate in a bottom-emitting OLED: first, the present invention combines two metal oxide transparent conductive film layers with a metal film layer including specific metals such as Ag, Al, Cu, Ca, Cr, Pd, Mg, Zn and / or Mo to form a light-transmitting electrode. Since these metals have good film-forming stability, excellent conductive properties, and easy processability, the OLED light-emitting device including the light-transmitting electrode has high color purity, excellent photoelectric efficiency and good driving stability; second, the light-transmitting electrode with the above structure included in the bottom-emitting OLED device of the present invention has good stability and processability, which makes the light source or display device prepared by the present invention have a good performance foundation; third, according to the present invention, the preparation process of the light-transmitting electrode is The process is consistent with the related processes of traditional flat panel displays, the process means are simple and easy to operate, the inheritance is good, the stability and consistent reproducibility are good, the cost-effectiveness is low, and the cost-effectiveness is high, which is conducive to realizing the cost-effectiveness of OLED devices and display devices thereof; fourthly, except for the structure and process related to the characteristics of the present invention, the other process methods for preparing OLED devices are the same as the traditional OLED device preparation process, such as the Tandem structure, the packaging process containing a desiccant, the packaging process containing a TFE film, etc. can all be applied to the manufacturing process of the present invention, so as to achieve the purpose of economical preparation; fifthly, by optimizing the thickness of the film layer in the light-transmitting electrode, the stability of the electrode, the conductivity of the electrode and the microcavity effect of the electrode are improved, and since the adhesion between the light-transmitting electrode film layer and the substrate and between the inner film layers of the light-transmitting electrode is improved, the stability of the device is significantly improved, and the efficiency of the device is also greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 It is a schematic structural diagram of the OLED device of the present invention, wherein the OLED is a bottom-emitting organic electroluminescent device.
[0012] Figure 2 Schematic diagram of the structure of an OLED according to a specific embodiment of the present invention, wherein the light-transmitting electrode is the anode.
[0013] Figure 3 Schematic diagram of the structure of an OLED according to another specific embodiment of the present invention, wherein the light-transmitting electrode is the cathode.
[0014] Figure 4 This is a schematic diagram comparing the angle-light intensity distribution of OLED devices based on surface light source testing, in which (1) and (2) respectively represent the angle-light intensity distribution diagrams of a conventional OLED device and the OLED device of the present invention.
[0015] Figure 5 It is a schematic diagram of the top view of the structure of a display device according to an embodiment of the present invention, wherein (3) represents the auxiliary electrode film layer.
[0016] Figure 6 It is a schematic side structural diagram of a display device according to another embodiment of the present invention.
[0017] Figure 7 The stacked OLED device of the present invention, wherein the organic functional material layer comprises two light-emitting units and a charge generation layer located between the two light-emitting units.
[0018] Figure 8 The 40° angle performance of the devices tested according to Examples 1-11 of the present application is represented by plotting the example number as the horizontal axis and the ratio of the light intensity in the direction perpendicular to the substrate to the light intensity in the direction at an angle of 40 degrees to the substrate as the vertical axis.
[0019] Figure 1-3 In , 5-7, the numbers represent the following meanings: 1 substrate, 2 transparent electrode, 2-1 first metal oxide transparent conductive film layer, 2-2 metal film layer, 2-3 second metal oxide transparent conductive film layer, 3-1 first hole transport region, 3-2 first light-emitting layer, 3-3 first electron transport region, 3-4 charge generation layer, 3-5 second hole transport region, 3-6 second light-emitting layer, 3-7 second electron transport region, 3 organic functional material layer, 4 reflective electrode. DETAILED DESCRIPTION
[0020] Any numerical range listed herein is intended to include all sub-ranges with the same numerical precision included in the listed range. For example, "1.0 to 10.0" means all sub-ranges (and including 1.0 and 10.0) included between the listed minimum value 1.0 and the listed maximum value 10.0, that is, all sub-ranges with a minimum value equal to or greater than 1.0 and a maximum value equal to or less than 10.0. Any maximum numerical limit listed herein is intended to include all smaller numerical limits included in this article, and any minimum numerical limit listed herein is intended to include all larger numerical limits included in this article. Therefore, the applicant reserves the right to modify the claims and the specification to clearly describe any sub-ranges falling within the scope clearly described herein.
[0021] In this application, when describing electrodes and organic electroluminescent devices, as well as other structures, the words "upper", "lower", "top" and "bottom" used to indicate orientation only indicate the orientation in a certain state, and do not mean that the related structure can only exist in the described orientation; on the contrary, if the structure can change its position, such as being inverted, the orientation of the structure will be changed accordingly. Specifically, in this application, the "bottom" or "lower" side of the electrode refers to the side of the electrode close to the substrate during the preparation process, and the opposite side away from the substrate is the "top" or "upper" side.
[0022] In the present application, "direct covering" means directly covering another film layer on the film layer by evaporation, spin coating or other process means.
[0023] The present invention provides an organic electroluminescent device, which comprises, from bottom to top, a substrate, a light-transmitting electrode, an organic functional material layer, and a reflective electrode, wherein the light-transmitting electrode comprises a first metal oxide transparent conductive film layer directly covering the substrate, a metal film layer directly covering the first metal oxide transparent conductive film layer, and a second metal oxide transparent conductive film layer directly covering the metal film layer.
[0024] The organic electroluminescent device of the present invention may be a bottom-emitting organic electroluminescent device, and may be a stacked organic electroluminescent device, without particular limitation.
[0025] The present invention will now be further described in conjunction with specific embodiments with reference to the accompanying drawings.
[0026] substrate
[0027] According to the present invention, the substrate of the organic electroluminescent device can use any substrate commonly used in organic electroluminescent devices. Examples are transparent substrates, such as glass or transparent plastic substrates; opaque substrates, such as silicon substrates; flexible PI film substrates. Different substrates have different mechanical strengths, thermal stability, transparency, surface smoothness, and waterproofness. Depending on the properties of the substrate, its use direction is different. In the present invention, a transparent substrate is preferably used. The thickness of the substrate is not particularly limited.
[0028] Light-transmitting electrode
[0029] According to the present invention, the light-transmitting electrode of the organic electroluminescent device can be an anode or a cathode. The light generated by the OLED device is projected into the air through the light-transmitting electrode and the substrate carrying the electrode. If the light-transmitting electrode is the anode of the OLED device, the adjacent OLED functional layer material is a hole injection and transmission material. If the light-transmitting electrode is the cathode of the OLED device, the adjacent OLED functional layer material is an electron injection and transmission material. At this time, the OLED device structure has an inverted feature.
[0030] Based on the above description, the characteristic structure of the OLED device described in this article starting from the substrate can include the following two forms:
[0031] 1. Substrate / transparent electrode / hole injection and transport layer... / reflective electrode, such as Figure 2 The example given;
[0032] 2. Substrate / transparent electrode / electron injection transport layer... / reflective electrode, such as Figure 3 The example given.
[0033] According to the present invention, an OLED device having the first characteristic structure is preferred, such as Figure 2 The example shown here is one in which the light-transmitting electrode is used as an anode of an organic electroluminescent device.
[0034] In the present invention, the light-transmitting electrode includes a first metal oxide transparent conductive film layer directly covering the substrate, a metal film layer directly covering the first metal oxide transparent conductive film layer, and a second metal oxide transparent conductive film layer directly covering the metal film layer; that is, the light-transmitting electrode is a composite film layer of the first metal oxide transparent conductive film layer / metal film layer / second metal oxide transparent conductive film layer.
[0035] According to the present invention, the first and second metal oxide transparent conductive film layers (TCO) mainly include metal oxides such as In, Sb, Zn, Cd, Sn, Al, Ca, Ga and their composite multi-element oxides, represented by indium tin oxide (ITO), indium zinc oxide (IZO), aluminum zinc oxide (AZO), gallium zinc oxide GZO, aluminum gallium zinc oxide AGZO, fluorine-doped tin oxide (FTO) or fluorine-doped SnO2 conductive glass (FTO: SnO2: F), which have good conductivity and higher transmittance in the visible light region (380-780nm), with an average transmittance greater than 80%. The preparation process of the TCO film includes vapor deposition, sputtering, sol-gel deposition and other processes. In addition to the above-mentioned metal oxide transparent conductive film materials, the following transparent conductive materials can also be listed: ZnO-In2O3-SnO2, ZnO-SnO2, ZnO-In2O3, Zn2In2O5-MgIn2O4, Zn2In2O5-In4Sn3O 12 , ZnSnO3-Zn2In2O5, ZnSnO3-In4Sn3O2, ZnSnO3-Zn2In2O5, GaInO3-In4Sn3O 12 , CuAlO2, CuGaO2, SrCu2O2. In some embodiments of the present invention, the materials of the first metal oxide transparent conductive film layer and the second metal oxide transparent conductive film layer each independently include or are selected from one or more of indium tin oxide ITO, indium zinc oxide IZO, aluminum zinc oxide AZO, gallium zinc oxide GZO, aluminum gallium zinc oxide AGZO, and fluorine-doped tin oxide FTO. The materials of the first metal oxide transparent conductive film layer and the second metal oxide transparent conductive film layer may be the same or different.
[0036] In the present invention, the first metal oxide transparent conductive film layer not only plays the conductive role required by the electrode film layer, but also needs to take into account the role of the light extraction film layer material (CPL: Cappinglayer) in the OLED device with microcavity characteristics. For OLEDs of different colors, the optimal thickness of the light extraction material film layer is different. For example, the optimal thickness of the film layer in the red light OLED device is thicker than that in the blue light OLED device. In addition, the thickness of the first metal oxide transparent conductive film layer is also related to the material of the metal film layer. The thickness of the first and second metal oxide transparent conductive film layers of the present invention is limited to a specific range according to the type of material of the metal film layer, and the current efficiency and service life of the device of the present invention are further improved.
[0037] In the present invention, the constituent materials of the metal film layer include but are not limited to Ag, Al, Cu, Ca, Cr, Pd, Mg, Zn or Mo. In some embodiments, the metal film layer material is selected from a combination of one or more metals of Ag, Al, Cu, Ca, Cr, Pd, Mg, Zn or Mo. In some optional embodiments, the metal film layer material includes or is selected from two or more metals of Ag, Al, Cu, Ca, Cr, Pd, Mg, Zn or Mo. In addition, the metal film layer may be a single metal material or a single-layer thin film material mixed with multiple metal materials or a multilayer superposition structure of multiple metal material film layers, and the metal material includes one, two or three of Ag, Al, Cu, Ca, Cr, Pd, Mg, Zn or Mo.
[0038] Preferably, the metal material includes at least one selected from Ag, Al, Cu, Ca, Cr or Mo. Therefore, according to some embodiments of the present invention, the metal film layer material is a single metal selected from one of Ag, Al, Cu, Ca, Cr, Pd, Mg, Zn or Mo, and the thickness of the first metal oxide transparent conductive film layer is 50-150nm, preferably 60-120nm. In addition, the metal film layer may be a multilayer superposition structure, wherein the material of each layer in the multilayer superposition structure includes or is selected from one or more metals selected from Ag, Al, Cu, Ca, Cr, Pd, Mg, Zn or Mo. According to some preferred embodiments of the present invention, the metal film layer material includes or is selected from the following metal combinations: 1) a combination of two or more metals in the first metal, the first metal is Ag, Al, Cu, Ca, Cr or Mo; or 2) a combination of any one or more metal materials in the first metal and a second metal, the second metal is Pd, Mg or Zn. In particular, the metal film layer material includes or is selected from a combination of two metals in the first metal, including a combination of Al and Cu, a combination of Al and Mo, a combination of Al and Ca, a combination of Al and Cr, a combination of Ag and Al, a combination of Ag and Cu, a combination of Ag and Mo, a combination of Ag and Ca, a combination of Ag and Cr, a combination of Cu and Cr, and a combination of Cu and Mo, and the mass ratio of the two metals is 2:3 to 10:1, preferably 1:1 to 9:1; especially in the combination of Ag and Al, Ag and Cu, Ag and Mo, Ag and Ca, and Ag and Cr, the mass ratio of Ag to Al, Cu, Mo, Ca or Cr is 2:3 to 10:1, preferably 1:1 to 9:1; in the combination of Cu and Cr, and Cu and Mo, the mass ratio of Cu to Cr or Mo is 2:3 to 10:1, preferably 1:1 to 9:1. In addition, the metal film layer material may also include or be selected from a combination of a first metal and a second metal, including a combination of Ag and Zn, a combination of Ag and Mg, a combination of Ag, Pd and Cu, a combination of Cu and Zn, a combination of Cu and Mg, a combination of Ag and Zn, and a combination of Ag, Pd and Cu, wherein the total mass ratio of the first metal to the metal material other than the first metal is 1:1 to 99:1. In the case where the metal film layer includes or is selected from a combination of metals, the thickness of the first metal oxide transparent conductive film layer is 10-150nm, preferably 20-120nm.
[0039] In particular, regarding the selection of material types and specific metals in the metal film layer, the following factors are mainly considered: first, a combination of two or more metals is more conducive to improving the stability of the metal film layer; second, according to the luminescent spectrum of the OLED device, a metal with low absorption and high reflectivity is selected within the spectral range. In the present invention, the metal film layer material is generally a single metal containing Ag or a combination with other metals. In the latter case, the mass ratio of Ag is not less than 50%, more preferably greater than 85%, based on the total mass of the combined metal. In the OLED of the present invention, in the metal film layer of the light-transmitting electrode, when a combined metal is used and the combined metal contains at least one of Ag and Al, the OLED device has excellent current efficiency. When the combined metal is a combination of Ag and Zn, a combination of Ag and Al, a combination of Al and Cu, a combination of Ag and Mg, a combination of Ag and Mo, a combination of Ag and Ca, or a combination of Ag, Pd and Cu, the OLED device has excellent current efficiency, improved color purity and good service life. When the material of the metal film layer is a metal containing only Ag or a combination of Ag and copper, the comprehensive performance of the OLED device of the present invention is further improved by adjusting the thickness of the first metal oxide transparent conductive film layer to be within the range of 30-150nm, especially within the range of 50-120nm or 60-120nm. Optionally, according to the present invention, the thickness of the metal film layer is 5-30nm, preferably 10-20nm.
[0040] The second metal oxide transparent conductive film layer of the present application also has other functions and significances, including the protective effect on the intermediate metal material film layer, and as an optical modulation layer to adjust the film thickness of the multilayer film structure between the reflective electrode and the metal material film layer to obtain the best light effect. For metal film materials with a film thickness of less than 30nm, both the scratch resistance and the stability in the atmospheric environment are far inferior to metal oxide transparent conductive film materials. Based on empirical summary, the thickness of the minimum metal oxide transparent conductive film material with a protective effect is above 5nm. In the present application, covering the metal oxide transparent conductive film material on both sides of the metal film layer can effectively protect the metal film material and improve the overall stability of the transparent electrode. On the other hand, because the bottom-emitting OLED device described in the present application has a strong microcavity effect, the optimal microcavity cavity length and the wavelength of the emitted light are in a one-to-one correspondence. Based on the intrinsic luminescence wavelength of the selected luminescent material, the light color and light efficiency of the luminescent material are optimal under the optimal optical path design, and there is also a so-called first resonance optimal optical path, second resonance optimal optical path or third resonance optimal optical path or higher-order resonance optimal optical path design. The organic functional material layer covering the light-transmitting electrode with microcavity characteristics of the present invention, if the second resonance optimal optical path design is selected, comprehensively considering factors such as the refractive index of the organic material and the metal phase shift, the microcavity length Y and the peak value X of the intrinsic spectrum of the organic electroluminescent material have the characteristic of Y=(0.6477X-88.3nm)±15nm, where Y is the sum of the thickness of the second metal oxide transparent conductive film layer and the total film thickness of the organic functional material layer sandwiched between the second metal oxide transparent conductive film layer and the reflective electrode. For example, for a blue light device with a spectral peak at 460nm, the microcavity length Y should be 209.6nm±15nm; for a green light device with a spectral peak at 530nm, the microcavity length Y should be 255nm±15nm; for a yellow light device with a spectral peak at 568nm, the microcavity length Y should be 279.6nm±15nm; for a red light device with a spectral peak at 625nm, the microcavity length Y should be 316.5nm±15nm; for a deep red light device with a spectral peak at 642nm, the microcavity length Y should be 327.5nm±15nm. It should be noted here that the aforementioned ±15nm film thickness deviation is, on the one hand, due to the errors caused by film thickness measurement and equipment, and on the other hand, based on the slight influence of the light-transmitting metal anode material on the film thickness of the multilayer organic material. Regardless of the influence, the error is basically within the range of plus or minus 15nm.If the third resonance optimal optical path design is selected, taking into account factors such as the refractive index of the organic material and the metal phase shift, the microcavity length Y and the peak value X of the intrinsic spectrum of the organic electroluminescent material have the characteristic of Y=(0.9247X-85.9)±15nm, where Y is the sum of the thickness of the second metal oxide transparent conductive film layer and the total film thickness of the organic functional material layer sandwiched between the second metal oxide transparent conductive film layer and the reflective electrode. For example, for a blue light device with a spectral peak at 460nm, the microcavity length Y should be 339.5nm±15nm; for a green light device with a spectral peak at 530nm, the microcavity length Y should be 404.2nm±15nm; for a yellow light device with a spectral peak at 568nm, the microcavity length Y should be 439.3nm±15nm; for a red light device with a spectral peak at 625nm, the microcavity length Y should be 492nm±15nm; for a deep red light device with a spectral peak at 642nm, the microcavity length Y should be in the range of 507.8nm±15nm. Therefore, the total film thickness of the third resonance optimal optical path design will be thicker than that of the second optical path design. Considering that the organic functional material layer also includes a light-emitting layer, the thickness of other functional layers of the electron injection conduction layer needs to be designed, and the preparation cost of the metal oxide transparent conductive film layer and the protective effect of the metal oxide transparent conductive film layer on the metal material are considered at the same time. Therefore, the limit thickness of the second metal oxide transparent conductive film layer is within 10-300nm, which can be selected as 10-300nm, preferably 15-150nm, and can also be 50-150nm or 60-120nm.
[0041] Therefore, according to some embodiments of the present invention, the thickness of the second metal oxide transparent conductive film layer and the organic functional material layer satisfies the following relationship: Y = (0.6477X-88.3nm) ± 15nm, wherein Y is the sum of the thickness of the second metal oxide transparent conductive film layer and the total film thickness of the organic functional material layer sandwiched between the second metal oxide transparent conductive film layer and the reflective electrode; X is the peak value of the photoluminescence spectrum of the light-emitting layer material of the organic electroluminescent device. Preferably, the organic electroluminescent device is a single-layer organic electroluminescent device or a stacked organic electroluminescent device. For each color light device, the Y value is as described above.
[0042] According to some other embodiments of the present invention, the thickness of the second metal oxide transparent conductive film layer and the organic functional material layer satisfies the following relationship: Y = (0.9247X-85.9) ± 15nm, wherein Y is the sum of the thickness of the second metal oxide transparent conductive film layer and the total film thickness of the organic functional material layer sandwiched between the second metal oxide transparent conductive film layer and the reflective electrode; X is the peak value of the photoluminescence spectrum of the light-emitting layer material of the organic electroluminescent device. Preferably, the organic electroluminescent device is a stacked organic electroluminescent device. For each color light device, the Y value is as described above.
[0043] In the embodiment of the present invention, the light-transmitting electrode can be set to different thicknesses, which serves as both the electrode of the device and the optical modulation layer (because it contains a second metal oxide transparent conductive film layer), and plays the role of driving the organic light-emitting device and adjusting the optical length. The stacked device has at least two light-emitting layers, that is, at least two identical or different X values. When the Y value satisfies any one of the above two relationship equations, the light of the corresponding X peak value is enhanced, the color purity of the peak value is improved, and the stray light of other wavelengths is greatly suppressed. Therefore, by setting the Y value, it is possible to enhance the light of a specific wavelength. If two light-emitting layers with different X values are required to emit light at the same time, the most ideal situation is that under the premise of fixed Y, the two X values and Y respectively satisfy two different relationship equations, and the light of two different colors is enhanced at the same time.
[0044] In order to make the organic electroluminescent device of the present invention have strong microcavity characteristics, it is necessary to make the sum of the thickness of the second metal oxide transparent conductive film layer and the total film thickness of the organic functional material layer sandwiched between the second metal oxide transparent conductive film layer and the reflective electrode and the peak value of the photoluminescence spectrum of the light-emitting layer material of the organic electroluminescent device satisfy the above relationship. Therefore, when the peak value of the photoluminescence spectrum of the organic electroluminescent material is constant, the thickness of the second metal oxide transparent conductive film layer or the thickness of any organic functional material layer sandwiched between the second metal oxide transparent conductive film layer and the reflective electrode can be adjusted to meet the above relationship. In some embodiments, the thickness of the first metal oxide transparent conductive film layer and the second metal oxide transparent conductive film layer are 10-150nm, preferably 20-120nm.
[0045] In this article, whether it is a single-layer organic electroluminescent device or a stacked organic electroluminescent device, the photoluminescence spectrum peak of the organic electroluminescent material used is obtained by evaporating a single layer of light-emitting layer material on alkali-free glass and testing its photoluminescence spectrum peak. The available testing equipment is, for example, HORIBA Fluorolog-3.
[0046] In some embodiments of the present invention, the thickness of the metal film layer is 5-30 nm, preferably 10-20 nm, which is conducive to making the light transmittance of the transparent electrode in the visible light region greater than 30%, preferably 30-80%, thereby improving the performance of OLED and improving light extraction efficiency and light color.
[0047] In some embodiments of the present invention, the total thickness of the light-transmitting electrode, that is, the sum of the thicknesses of the first metal oxide transparent conductive film layer, the second metal oxide transparent conductive film layer and the metal film layer is greater than 105nm and less than 330nm, and can be selected from 100nm to 270nm, more preferably from 150nm to 250nm, and most preferably from 180nm to 210nm.
[0048] In some embodiments of the present invention, the thickness of the first metal oxide transparent conductive film layer is 30-150nm, preferably 50-120nm, the thickness of the metal film layer is 5-30nm, preferably 10-20nm; the thickness of the second metal oxide transparent conductive film layer is 10-300nm, preferably 15-150nm.
[0049] In the present invention, because the light-transmitting electrode has a microcavity adjustment function for the electroluminescence (EL) light emission of the OLED device, when the OLED device is treated as a surface light source and its light intensity-angle distribution is tested, its distribution will show non-Lambertian characteristics, and the light intensity distribution is related to the light-transmitting electrode structure and film thickness, and the film thickness of the OLED multilayer film. In the light emitted to the surroundings, the ratio of the light intensity in the direction perpendicular to the substrate to the light intensity in the direction of the substrate at an angle of 40 degrees is preferably greater than 1.5 times, preferably greater than 2 times, and more preferably greater than 2.3 times. Therefore, the use of the light-transmitting electrode of the present invention can increase the light intensity perpendicular to the substrate and achieve the best color purity effect of the OLED device. Therefore, in some embodiments of the present invention, when the organic electroluminescent device of the present invention is used as a surface light source for testing, the ratio of the light intensity in the direction perpendicular to the substrate to the light intensity in the direction of the substrate at an angle of 40 degrees in the light emitted to the surroundings by the organic electroluminescent device is greater than 1.5 times, preferably greater than 2 times.
[0050] In an embodiment of the present invention, because the light-transmitting electrode is a multi-layer film structure, and both the metal material film layer and the transparent metal oxide film layer have good conductivity, this contributes to the good conductivity of the OLED light-transmitting electrode, and the square resistance of the light-transmitting electrode can be less than 7Ω / □, preferably less than 5Ω / □.
[0051] In some preferred embodiments of the present invention, for red, blue, green, yellow and amber OLED devices, the light-transmitting electrode is used as an anode. In the light-transmitting electrode, the material of the first metal oxide transparent conductive film layer can be listed as an oxide conductive material such as ITO, AZO, GZO, AGZO or IZO, and its thickness is 30-150nm, preferably 50-120nm, and the metal film layer is a single metal material Ag or Mo; the thickness of the second metal oxide transparent conductive film layer is 10-300nm, preferably 15-150nm. At the same time, the ratio of the thickness of the first metal oxide transparent conductive film layer to the metal film layer is in the range of 2.5:1 to 12.5:1, preferably 5:1 to 7:1, and the obtained device has excellent current efficiency, improved color purity and good service life.
[0052] In other preferred embodiments of the present invention, for red, blue, green, yellow and amber OLED devices, the light-transmitting electrode serves as an anode, in the light-transmitting electrode, the material of the first metal oxide transparent conductive film layer can be listed as oxide conductive materials such as ITO, AZO, GZO, AGZO or IZO, and its thickness is 30-150nm, preferably 50-120nm, and the metal film layer is a combined metal material, and the thickness of the second metal oxide transparent conductive film layer is 10-300nm, preferably 15-150nm. When the combined metal is selected from a combination of Ag and Cu (Ag:Cu mass ratio of 1:1 to 9:1), a combination of Ag and Al (Ag:Al mass ratio of 1:1 to 9:1), a combination of Ag and Mo (Ag:Mo mass ratio of 1:1 to 9:1), a combination of Al or Cu (Al:Cu mass ratio of 1:1 to 9:1), or a combination of Ag:Ca (Ag:Ca mass ratio of 1:1 to 9:1), the obtained device has excellent current efficiency, improved color purity and good service life.
[0053] In some other preferred embodiments of the present invention, for red, blue, green, yellow and amber OLED devices, the light-transmitting electrode is used as an anode, in the light-transmitting electrode, the material of the first metal oxide transparent conductive film layer can be listed as an oxide conductive material such as ITO, AZO, GZO, AGZO or IZO, and its thickness is 30-150nm, preferably 50-120nm, and the metal film layer is a combined metal material, and the thickness of the second metal oxide transparent conductive film layer is 10-300nm, preferably 15-150nm. The combined metal is selected from Ag and Mg combination (Ag:Mg mass ratio is 1:1 to 9:1), Ag and Zn combination (Ag:Zn mass ratio is 1:1 to 9:1), or Ag, Pd and Cu combination (Ag:Pd:Cu mass ratio is 95:1:1 to 99:1:1), and the obtained device has excellent current efficiency, improved color purity and good service life.
[0054] In some embodiments of the present invention, in the light-transmitting electrode, the first metal oxide transparent conductive film layer is the same as the second metal oxide transparent conductive film layer. The OLED device is a single color device of red, green and blue.
[0055] The OLED device can be a stacked structure, for example, including two light-emitting layers, for example, both light-emitting layers are single red, green and blue monochromatic light-emitting layers, or one of the light-emitting layers is a red light-emitting layer and the other is a blue light-emitting layer, or one of the light-emitting layers is a multi-color light-emitting layer of a combination of red and green light-emitting materials and the other is a single blue light-emitting layer, or other combinations of different colors. In the preferred light-transmitting electrode of the present invention, the stacked OLED device includes the light-transmitting electrode described in any one of the three preferred embodiments above, and the stacked OLED device prepared thereby also has excellent current efficiency, improved color purity and service life.
[0056] In the OLED device of the present invention, the preparation process of each film layer constituting the light-transmitting electrode can be, for example, vacuum evaporation, sputtering, etc., preferably, the sputtering process method is adopted. For the patterning of the light-transmitting electrode, the patterned graphics with a certain accuracy can be realized based on the selection of the mask (mask), or the patterning of the electrode can be realized by photolithography combined with etching.
[0057] Organic functional material layer
[0058] The organic functional material layer is also called an OLED multilayer film, which may include multiple light-emitting units and a charge generation layer located between the light-emitting units. The structure of each light-emitting unit includes: a hole transport region, a light-emitting region, and an electron transport region. According to the present invention, the organic functional material layer of the organic electroluminescent device includes a hole transport region, a light-emitting region, and an electron transport region.
[0059] Hole transport region
[0060] In the organic electroluminescent device of the present invention, the hole transport region includes a hole injection layer, a hole transport layer and a hole transport auxiliary layer (electron blocking layer), and all these functional layer materials can be processed by conventional techniques in the art, such as solvent wet processing or vacuum evaporation.
[0061] Hole injection layer
[0062] According to the present invention, when the light-transmitting electrode is used as the anode of the OLED device, the adjacent hole injection layer can use a material that is in contact with the anode and has a good positive charge carrier injection effect, that is, a hole injection material, such as a hole-type material that can be wet processed, and its examples include or are selected from the following types of substances:
[0063]
[0064] Among the above materials, PEDOT:PSS is a water-soluble wet-processing cavitation material; Polymer1 is a solvent-based wet-processing cavitation polymer material, wherein R1 and R2 represent aromatic groups, N and M represent the number of specific group polymerizations, and their structures and molecular weights can be adjusted as needed. Optionally, R1 and R2 are independently selected from substituted or unsubstituted C6-C 60 aryl or substituted or unsubstituted 5-60 membered heteroaryl; more optionally, R1 and R2 are independently selected from substituted or unsubstituted phenyl, substituted or unsubstituted naphthyl, substituted or unsubstituted biphenyl, substituted or unsubstituted terphenyl, substituted or unsubstituted furyl, substituted or unsubstituted benzofuranyl, substituted or unsubstituted dibenzofuranyl, substituted or unsubstituted thienyl, substituted or unsubstituted benzothienyl, substituted or unsubstituted dibenzothienyl, substituted or unsubstituted fluorenyl, substituted or unsubstituted diphenylfluorenyl, substituted or unsubstituted carbazolyl; N and M are positive integers greater than 5; n is a positive integer greater than 5.
[0065] In the aforementioned substituted or unsubstituted groups, the substituent of the substituted group / the substituent replacing the above group is selected from one or more of a deuterium atom, a methyl group, a deuterated methyl group, an ethyl group, a tert-butyl group, an adamantyl group, a phenyl group, a biphenyl group, and a naphthyl group.
[0066] For solvent-based wet-processed hole-type polymer materials, Polymer 1 is only exemplary. For this type of material, companies such as DuPont in the United States, Merck in Germany, Sumitomo Chemical in Japan, Nissan Chemical and Mitsubishi Chemical have conducted a lot of research, which can be used in the present invention and are not listed here. In order to improve the electrode injection effect of wet-processed hole-type materials such as Polymer 1 and achieve ohmic contact with the electrode, it is also possible to add P-type doping materials to the polymer material. The so-called P-type doping material can be selected from organic materials with LUMO energy levels greater than 5eV such as cyano groups and fluorine groups in the molecular structure, and more preferably organic materials with LUMO energy levels greater than 5.2eV, such as using Lewis acids including PD-A as PD doping materials.
[0067] According to the present invention, when the light-transmitting electrode is used as the anode of the OLED device, in order to achieve a good hole injection effect from the anode to the organic functional material layer, the hole injection layer is a P-doped characteristic organic film layer, and its basic characteristic is that the aromatic amine hole material is doped with a P-type doping material. After research, it was found that when the optimal value of the energy level difference between the LUMO of the P-doped material and the HOMO of the aromatic amine hole material is less than 0.3eV, a good charge transfer state (CT state: charge transfer state) can be formed, thereby achieving the effect of their best combination.
[0068] In the present invention, the aromatic amine hole material can be, for example, an aromatic amine hole injection conductive material, and the aromatic amine hole material includes a monoaromatic amine hole material, a diaromatic amine or other polyaromatic amine hole materials.
[0069] According to some optional embodiments of the present invention, the organic functional material layer comprises a hole transport region, a light emitting region and an electron transport region, the hole transport region comprises a hole injection layer and a hole transport layer, the hole injection layer is selected from a host material (i.e., a hole transport material) represented by the general formula (I-1) or the general formula (I-2), and a doping material represented by the general formula (I-3), wherein the monoaromatic amine hole material has a structure of the general formula (I-1), and the diaromatic amine hole material has a structure of the general formula (I-2):
[0070] NC—Ar4 (I-3)
[0071] Ar1-Ar4 are independently selected from substituted or unsubstituted C6-C 60 substituted or unsubstituted 5-60 membered heteroaryl, optionally, any two of Ar1-Ar3 in formula (I-1) are C 1-6 Alkyl, optionally 2-propylene connected; the substituents replacing the above groups are selected from: C1-C 10 Alkyl, C3-C 10 Cycloalkyl, C6-C 60 aryl, 5-60 membered heteroaryl; L1, L2 are phenylene. Optionally, Ar1-Ar4 are independently selected from unsubstituted or substituted phenyl, biphenyl, terphenyl, carbazolyl, N-phenylcarbazolyl, 9,9-dimethylfluorenyl, naphthyl, 9,9'-spirobifluorenyl or a combination thereof, and in the case of substitution, the substituent may be a C1-C6 alkyl, preferably a methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, sec-butyl or tert-butyl.
[0072] Preferably, the host materials represented by general formula (I-1) and general formula (I-2) are selected from the following specific compounds:
[0073]
[0074]
[0075] In the present invention, the purpose of adding a P-type doping material is to improve the conductivity of carriers and reduce the driving voltage of the organic electroluminescent device, thereby improving the performance of the organic electroluminescent device. The P-type doping material is selected from quinone derivatives, such as tetracyanoquinodimethane (TCNQ) and 2,3,5,6-tetrafluoro-tetracyano-1,4-benzoquinodimethane (F4-TCNQ); or hexaazatriphenylene derivatives, such as 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene (HAT-CN); or cyclopropane derivatives, such as 4,4',4"-((1E,1'E,1"E)-cyclopropane-1,2,3-trimethylenetris(cyanoformyl))tris(2,3,5,6-tetrafluorobenzyl); or metal oxides, such as tungsten oxide and molybdenum oxide, but not limited thereto.
[0076] Preferably, the doping material of general formula (I-3) is selected from the following compounds:
[0077]
[0078] In the hole injection layer of the present invention, the hole transport material is doped with the P-type material, wherein the doping ratio of the P-type material is 0.1-20 wt %, preferably 0.1-5 wt %, more preferably 0.1-3 wt %, based on the mass of the hole transport material.
[0079] For the non-P-doped hole injection layer, the hole injection material used may be a material known in the prior art and applied in this field.
[0080] According to some embodiments of the present invention, the hole injection layer comprises a host material having the general formula (I-1) and a dopant material having the general formula (I-3), or a single film layer material having (I-3);
[0081] NC—Ar4 (I-3)
[0082] Ar1-Ar4 are the same or different, have the above definition and independently have a molecular weight of 50,000 to 50,000. Preferably, the host material of general formula (I-1) is selected from the aromatic amine hole materials HT1 to HT16 above; the doping material of general formula (I-3) is selected from the compounds of P1, P3 to P4, P6 to P16 above.
[0083] There are also some metal compound materials with semiconductor properties that can be adjacent to the anode and used as hole injection functional materials for OLED devices, including metal oxide materials, metal halide semiconductor materials, etc., such as MoxOy, VxOy, WxOy, FexCly, NixOy and other types of materials. Here, x and y are selected from positive integers in the range of 1 to 5, representing different valence bond structures of the compound, different preparation processes, and the formed metal oxide film may be a composition of multivalent bond structure, rather than a fixed single valence bond compound. Therefore, in some embodiments, the organic functional material layer comprises a hole transport region, a light emitting region and an electron transport region, the hole transport region comprises a hole injection layer and a hole transport layer, the hole injection layer material is selected from one or more of inorganic metal oxides and inorganic metal halides; the inorganic metal oxide is selected from one or more of MoxOy, VxOy, WxOy or NixOy, and the inorganic metal halide is selected from FexCly; wherein x and y are selected from positive integers in the range of 1 to 5.
[0084] Hole transport layer
[0085] In the present invention, the material of the hole transport layer of the OLED device is selected from the aromatic amine hole materials described above for the hole injection layer, and the aromatic amine hole materials used in the hole transport layer and the hole injection layer can be the same or different. Regardless of the selection, the purpose is to achieve a good injection and transport effect of hole carriers.
[0086] The thickness of the hole injection layer of the present invention may be 5 to 250 nm, preferably 5 to 100 nm, and more preferably 5 to 20 nm, but the thickness is not limited to these ranges.
[0087] The thickness of the hole transport layer of the present invention may be 5 to 200 nm, preferably 10 to 150 nm, and more preferably 20 to 100 nm, but the thickness is not limited to these ranges.
[0088] Hole transport layer (EBL)
[0089] The material used as the EBL layer is used to improve the transport efficiency of hole carriers in the light-emitting layer and improve the carrier recombination efficiency. The HOMO energy level of the EBL material is between the HOMO energy level of the hole transport layer HTL material and the HOMO energy level of the light-emitting layer EML main material, which is conducive to the injection of holes from the positive electrode into the light-emitting layer. At the same time, the EBL material is required to have good hole mobility, which is conducive to improving hole transport and reducing the application power of the device. The LUMO energy level of the EBL material is higher than the LUMO energy level of the light-emitting layer main material, which plays the role of electron blocking, that is, the EBL material is required to have a wide bandgap (Eg). In the phosphorescent device system, its triplet state (T1) energy level is higher than the T1 energy level of the main material in the light-emitting layer, which can play the role of blocking the energy loss of the light-emitting layer material. The EBL material that meets the above conditions can be a triarylamine derivative, a fluorene derivative, a spirofluorene derivative, a dibenzofuran derivative, a carbazole derivative, etc. Among them, preferred are triarylamine derivatives, such as N,N-di(4-(dibenzo[b,d]furan-4-yl)phenyl)-[1,1':4',1"-terphenyl]-4-amine; spirofluorene derivatives, such as N-([1,1'-diphenyl]-4-yl)-N-(9,9-dimethyl-9H-furan-2-yl)-9,9'-spirobi[fluorene]-2-amine; dibenzofuran derivatives, such as N,N-di([1,1'-biphenyl]-4-yl)-3'-(dibenzo[b,d]furan-4-yl)-[1,1'-biphenyl]-4-amine, but are not limited thereto.
[0090]
[0091] In the present invention, the material of the hole transport auxiliary layer is preferably the above-mentioned EB-1, EB-2 and / or EB-3; the thickness of the hole transport auxiliary layer is 2-200 nm, preferably 5-50 nm.
[0092] Optionally, the thickness of the hole transport auxiliary layer is adjusted to meet the range of the microcavity length Y mentioned above.
[0093] Emission layer (EML)
[0094] The light-emitting layer can be arranged on the hole transport region. The materials used in the light-emitting layer of the organic electroluminescent device of the present invention can be divided into host materials and dopant materials according to their different functions; they can be divided into phosphorescent materials, fluorescent materials, thermally activated fluorescent materials, etc. according to the different characteristics of the materials used; they can be divided into TTA fluorescent materials, phosphorescent materials, TADF sensitized system materials, etc. according to the different energy transfer and luminescence mechanisms. There is no special restriction on the selection of various types of materials.
[0095] The material of the light-emitting layer is a material that emits visible light by receiving holes and electrons from the hole transport layer and the electron transport layer respectively, and combining the received holes and electrons. Specific examples thereof include metal complexes of hydroxyquinoline derivatives, various metal complexes, anthracene derivatives, distyrylbenzene derivatives, pyrene derivatives, oxazole derivatives and poly(p-phenylene vinylene) derivatives, but are not limited thereto. In addition, in the above-mentioned organic electroluminescent device, the three pixels of red, green and blue are all composed of a host material and a guest material. The guest material includes two major categories: fluorescent materials and phosphorescent materials. Compared with fluorescent luminescent materials, phosphorescent luminescent materials can simultaneously utilize singlet and triplet excitons during the luminescence process, and theoretically the internal quantum efficiency can reach 100%, thereby greatly improving the luminescence efficiency of the light-emitting device.
[0096] As the host material and guest material of the light-emitting layer of the organic electroluminescent device of the present invention, the light-emitting layer materials for organic electroluminescent devices known in the prior art can be used. The host materials of the red, green and blue pixel light-emitting layers not only need to have bipolar charge transfer characteristics, but also need to have appropriate energy levels, which can effectively transfer the excitation energy generated by the recombination of electrons and holes to the guest light-emitting materials. The host material can be, for example, thiazole derivatives, benzimidazole derivatives, polydialkylfluorene derivatives or 4,4'-bis(9-carbazolyl)biphenyl (CBP), distyryl arylene derivatives, stilbene derivatives, carbazole derivatives, triarylamine derivatives, anthracene derivatives, pyrene derivatives, triphenylene derivatives, etc.
[0097] In the above-mentioned organic electroluminescent device, the guest luminescent material can be a simple fluorescent material, a phosphorescent material, or a combination of different fluorescent materials and phosphorescent materials. Preferably, blue luminescence is generated by fluorescent materials, and green and red luminescence are generated by phosphorescent materials. As a fluorescent guest material for generating luminescence, it is not only required to have an extremely high fluorescence quantum luminescence efficiency, but also to have an appropriate energy level, which can effectively absorb the excitation energy of the host material to emit light. For example, blue fluorescent materials include distyrylamine derivatives, pyrene derivatives, triphenylene derivatives, anthracene derivatives, benzoxazole derivatives, benzothiazole derivatives, benzimidazole derivatives, chrysene derivatives, diazine derivatives, distyrylbenzene derivatives, tetraphenylbutadiene derivatives, etc. One or more of quaternary compounds, biphenyl compounds, benzimidazole compounds, benzoxazole compounds, benzoxadiazole compounds, styrylbenzene compounds, butadiene compounds, naphthalene imide compounds, perillene compounds, aldazine compounds, cyclopentadiene compounds, styrylamine compounds, coumarin compounds, aromatic xylene theophylline compounds, and polyphenyl compounds can also be listed. Specific examples of phosphorescent materials include phosphorescent materials of metal complexes of iridium, platinum, etc. For example, green phosphorescent materials such as Ir(ppy)3[fac-tri(2-phenylpyridine)iridium], blue phosphorescent materials such as FIrpic, FIr6, and red phosphorescent materials such as Btp2Ir(acac) can be used. In some embodiments, the organic functional material layer includes two light-emitting units, wherein the light-emitting region of one light-emitting unit includes a blue light-emitting material, and the light-emitting region of the other light-emitting unit includes a red light-emitting material.
[0098] In addition, the host-guest materials for generating light in the organic electroluminescent device can also adopt compounds disclosed in the following patents or patent applications, which include: U.S. patents or patent applications: US20080193797, US20080220285, US20080128009, US20090110957, US20100295444, US20110114889, US20110042655, US20110147716, US20110284799, US20120126180, US20120112169, US 2012011216, US7846558, US8173275; Japanese patents or patent applications: JPA2007223904, JPA2008214332, JPA2008291271, JPA2008545630, JPA2009010181, JPA2009505995, JPA2010238880, JPA2010241687, JPA201002776, JPA2011216640, JPA2012080093; International patents or patent applications: WO12007032161, WO12007032162.
[0099] When a fluorescent guest is used, the guest material is preferably present in an amount of 0.1 to 20% by weight based on the weight of the host material.
[0100] In addition, in order to obtain a high-efficiency organic electroluminescent device, in addition to using the above-mentioned fluorescent or phosphorescent host-guest materials, the light-emitting layer can also use a doping material, or use multiple doping materials. The doping material can be a fluorescent material, a delayed fluorescence (TADF) material or a phosphorescent material or a combination thereof.
[0101] In a specific embodiment of the present invention, the light-emitting layer used in the blue OLED device is a host material BH-1 and a guest material BD-1 in a mass ratio of 97:3; the light-emitting layer used in the red OLED device is a host material RH-1 and a guest material RD-1 in a mass ratio of 97:3; the light-emitting layer used in the green OLED device is a host material GH-1, GH-2 and a guest material GD-1 in a mass ratio of 47:47:6; the light-emitting layer used in the yellow OLED device is a host material GH-1, GH-2 and a guest material YD-1 in a mass ratio of 47:47:6; the light-emitting layer used in the amber OLED device is a host material GH-1, GH-2 and a guest material AD-1 in a mass ratio of 47:47:6.
[0102]
[0103]
[0104] The thickness of the light-emitting layer of the present invention may be 5-60 nm, preferably 10-50 nm.
[0105] The vacuum deposition process can be used to prepare the light-emitting layer in the OLED device. In this process, a light-shielding mask is required to be used to carefully prepare the red (R), green (G), blue (B) light-emitting layer, yellow (Y) light-emitting layer, and amber (A) light-emitting layer at the corresponding positions through the vacuum deposition process. However, when using the spin coating process or laser-induced thermal imaging processing, it is not necessary to use a light-shielding mask to compose the pattern.
[0106] Electron transport region
[0107] According to the present invention, the electron transport region may include, from bottom to top, a hole blocking layer, an electron transport layer and an electron injection layer disposed on the light emitting layer, but is not limited thereto.
[0108] Hole Blocking Layer (HBL)
[0109] The hole blocking layer is used to block the holes injected from the anode from passing through the light-emitting layer and entering the cathode, thereby extending the life of the device and improving the efficiency of the device. The hole blocking layer of the present invention can be arranged on the light-emitting layer. As the hole blocking layer material of the organic electroluminescent device of the present invention, compounds with hole blocking effects known in the prior art can be used, for example, metal complexes of hydroxyquinoline derivatives such as bathocuproine (referred to as BCP), aluminum (III) bis (2-methyl-8-quinoline) -4-phenylphenol salt (BAlq), various rare earth complexes, oxazole derivatives, triazole derivatives, triazine derivatives, etc. The thickness of the hole blocking layer of the present invention can be 2-20nm, preferably 5-15nm and more preferably 5-10nm.
[0110] Electron Transport Layer (ETL)
[0111] The electron transport layer may be disposed between the hole blocking layer and the electron injection layer (if present). The electron transport layer material is a material that easily receives electrons from the cathode and transfers the received electrons to the light-emitting layer. Preferably, the material has a high electron mobility. As the electron transport layer of the organic electroluminescent device of the present invention, the electron transport layer materials for organic electroluminescent devices known in the prior art can be used, for example, metal complexes of hydroxyquinoline derivatives represented by Alq3 and BAlq, various metal complexes, triazole derivatives, triazine derivatives such as 2,4-bis(9,9-dimethyl-9H-fluorene-2-yl)-6-(naphthalene-2-yl)-1,3,5-triazine (CAS No.: 1459162-51-6), imidazole derivatives such as 2-(4-(9,10-di(naphthalene-2-yl)anthracene-2-yl)phenyl)-1-phenyl-1H-benzo[d]imidazole (CAS No.: 561064-11-7, commonly known as LG201), oxadiazole derivatives, carbodiimide derivatives, quinoxaline derivatives, phenanthroline derivatives, silicon-based compound derivatives, etc.
[0112]
[0113] In the present invention, the materials of the electron transport layer of the OLED are ET-1 and Liq. In the present invention, the thickness of the electron transport layer may be 10-80 nm, preferably 20-60 nm, and more preferably 25-45 nm.
[0114] Electron injection layer (EIL)
[0115] The electron injection layer can be arranged between the electron transport layer and the cathode. The electron injection layer material is generally preferably a material with a low work function, so that electrons are easily injected into the organic functional material layer. As the electron injection layer material of the organic electroluminescent device of the present invention, the electron injection layer material for organic electroluminescent devices known in the prior art can be used, for example, lithium; lithium salts, such as 8-hydroxyquinoline lithium, lithium fluoride, lithium carbonate or lithium azide; or cesium salts, cesium fluoride, cesium carbonate or cesium azide. In some embodiments of the present invention, the material of the electron injection layer is selected from ytterbium Yb. The thickness of the electron injection layer can be 0.1-15nm, preferably 0.5-10nm. In order to enable the organic electroluminescent device to obtain a low-voltage driving effect, the electron injection layer and the electron transport layer of the organic electroluminescent device usually adopt an N-type doped structure. The materials that can be used as N-type doping include metal materials with low work function, such as Li, Cs, K, Yb, etc., and also include Ag-doped coordination transport materials containing o-phenanthroline or bipyridine, etc., and some metal material oxides, fluorides or nitrides, etc., such as Li2O, CsF, Li3N, CsN, etc.
[0116] Charge generation layer
[0117] The organic electroluminescent device described in the present application may be a stacked organic electroluminescent device, which includes two or more light-emitting units. Each light-emitting layer unit of the stacked organic electroluminescent device is connected by a charge generation layer. In order to improve the performance of the stacked organic electroluminescent device, the charge generation layer must have the ability to transfer electrons to the electron transport layer and transfer holes to the hole transport layer. The charge generation layer must include at least one N-type metal material doped organic compound layer, and the metal material is Li, Ca, Ag, Cs or Yb.
[0118] In the present invention, the organic functional material layer includes a plurality of light-emitting units and a charge generation layer, and the charge generation layer is located between two light-emitting units. Examples of the charge generation layer include compounds of phenanthroline structure, metal materials selected from one of Li, Ca, Ag, Cs or Yb. In some embodiments of the present invention, the charge generation layer includes ET-2 and Yb. The thickness of the charge generation layer may be 5-20nm (10nm in the embodiment).
[0119]
[0120] Therefore, according to some embodiments of the organic electroluminescent device described in the present application, the organic functional material layer includes two or more light-emitting units and a charge generation layer, and the light-emitting units each independently include a hole transport region, a light-emitting region, and an electron transport region; the charge generation layer is located between two adjacent light-emitting units, and preferably the charge generation layer includes a compound with a phenanthroline structure, and the thickness of the charge generation layer is 5 to 15 nm. In some embodiments of the present application, the charge generation layer is also doped with a metal material, and the metal material is one or more of Li, Ca, Ag, Cs or Yb; the doping ratio of the metal material is 0.1-3.1% by weight, based on the weight of the compound containing the phenanthroline structure.
[0121] In the stacked organic electroluminescent device of the present invention, it includes, from bottom to top, a substrate, a transparent electrode (including a first metal oxide transparent conductive film layer, a metal film layer and a second metal oxide transparent conductive film layer), a first light-emitting unit (including a hole transport region, a light-emitting layer and an electron transport region in sequence), a charge generation layer, a second light-emitting unit (including a hole transport region, a light-emitting layer and an electron transport region in sequence), and a reflective electrode. The first and second light-emitting units may be the same or different, for example, both are red light-emitting units, both are yellow light-emitting units, both are amber light-emitting units, or are red, blue, yellow, amber, etc. light-emitting units.
[0122] Reflective electrode
[0123] The reflective electrode is an electrode that reflects the light generated by the OLED device and projects it into the air after passing through the transparent electrode based on the mirror reflection effect. The reflective electrode can be arranged above the electron transport region. The reflective electrode can be a cathode. Suitable materials for use as a cathode include: metals or alloys of several metals, such as Al, Mg, Ca, Li, Yb, Ag, Mg / Ag, Yb / Ag, Mg / Ag, Yb / Ag, Li / Ag, Al / Ag, Ca / Ag, etc. Optionally, the reflective electrode includes at least one or more metals selected from Ag, Al, Ca, and Mg. Preferably, the mass ratio of Al or Ag in the reflective electrode material is preferably greater than 90%. This electrode is required to have good conductivity, reflectivity, chemical form, stability, etc.
[0124] The electrode layer can be made by vacuum evaporation, vapor deposition, sputtering or chemical vapor deposition, preferably by vacuum evaporation.
[0125] The organic electroluminescent device may further include an encapsulation structure. The encapsulation layer material can effectively prevent oxygen, low molecular weight components and moisture from penetrating into the OLED, thereby improving the overall stability of the organic electroluminescent device. The encapsulation may be performed using desiccant encapsulation, UV glue encapsulation (Dam only encapsulation), UV glue and filling glue encapsulation (Dam & Fill encapsulation), or glass glue encapsulation (Frit encapsulation). In this embodiment, UV glue and filling glue encapsulation are preferably used.
[0126] Preparation method of OLED
[0127] In the process of preparing an organic electroluminescent device, for example, the organic electroluminescent device of the present invention can be prepared by laminating an anode, a functional material layer and a cathode successively on a substrate. The preparation method includes a physical vapor deposition method, such as a sputtering method or an electron beam vapor method, or a vacuum evaporation method, but is not limited thereto. In addition, the above-mentioned compound can be used to form a functional material layer by, for example, a vacuum deposition method, a vacuum evaporation method or a solution coating method. Wherein, the solution coating method means a spin coating method, a dip coating method, a jet printing method, a screen printing method, a spray method and a roller coating method, but is not limited thereto. Vacuum evaporation means that in a vacuum environment, the material is heated and plated onto a substrate. In the present invention, it is preferred to use a vacuum evaporation method to form each of the layers.
[0128] The structure of OLED will be described in detail below with reference to the accompanying drawings.
[0129] Figure 1The basic structure of the OLED device of the present invention is shown. The meanings of the reference numerals in the figure refer to the description of the figure. Under the action of the electric field, the OLED device injects carriers into the organic functional material layer through the transparent electrode and the reflective electrode respectively, and the carriers are recombined and excited in the light-emitting layer to generate electroluminescence, and the light is reflected by the reflective electrode through the transparent electrode and emitted to the external environment through the substrate.
[0130] Figure 2 The schematic diagram of the structure of an OLED according to a specific embodiment of the present invention is shown, wherein the light-transmitting electrode is the anode; thus, the hole transport region 3-1 in the organic functional material layer 3 is arranged on the light-transmitting electrode. Under the action of an electric field, the OLED device injects holes from the light-transmitting electrode (anode) into the organic functional material layer, and injects electrons from the reflective electrode (cathode) into the organic functional material layer. The electrons and holes recombine and excite in the OLED light-emitting layer to generate electroluminescence, and the light is reflected by the reflective electrode, passes through the light-transmitting electrode, and is emitted to the external environment through the substrate.
[0131] Figure 3 A schematic diagram of the structure of an OLED according to another specific embodiment of the present invention is shown, wherein the light-transmitting electrode is a cathode; thus, the 3-3 electron transport region in the organic functional material layer 3 is arranged on the light-transmitting electrode. Under the action of an electric field, the OLED device injects electrons from the light-transmitting electrode (cathode) into the organic functional material layer, and injects holes from the reflective electrode (anode) into the organic functional material layer. The electrons and holes recombine and excite in the OLED light-emitting layer to generate electroluminescence, and the light is reflected by the reflective electrode, passes through the light-transmitting electrode, and is emitted to the external environment through the substrate.
[0132] According to the present invention, when the light-transmitting electrode is used as the cathode of the OLED device, the bottom-emitting OLED device structure is an OLED device with inverted characteristics. In order to achieve a good electron injection effect from the cathode / light-transmitting electrode to the organic functional material layer of the OLED, the specific method adopted includes: doping the electron transport layer with a metal material or a metal compound material, or by doping a single metal material or an organic metal compound material in the electron transport layer material, or by doping an inorganic metal compound material in the electron transport layer material. The metal material doped in the electron transport layer material should have a lower work function, preferably within 0-2.9 eV, and examples include Na, K, Rb, Cs, Sr, Ba, Li, Yb, Ca and other materials. For the structure of the inverted characteristic OLED device, from bottom to top, it includes a light-transmitting electrode (cathode), an electron injection layer, an electron transport layer, a hole blocking layer, a light-emitting layer, a hole transport layer, a hole injection layer, and a reflective electrode (anode).
[0133] Figure 4The angle-light intensity distribution diagram of the OLED device of the present invention and the conventional OLED device is shown. Assuming that the organic electroluminescent device is a surface light source, in the angle-light intensity distribution diagram in arrow (1), the ratio of the light intensity in the direction perpendicular to the substrate to the light intensity in the direction at an angle of 40 degrees to the substrate is small, which is the light-emitting characteristic of the conventional OLED device using a metal oxide conductive film as an anode; arrow (2) is the angle-light intensity distribution diagram of the OLED device of the present invention, which is characterized in that the light intensity in the direction perpendicular to the substrate is the strongest, and the ratio of the light intensity in the direction perpendicular to the substrate to the light intensity in the direction at an angle of 40 degrees to the substrate is greater than 1.5 times, preferably greater than 2 times, and more preferably between 2.5 times and 2.8 times. It can be seen that when the OLED device of the present invention uses the composite film layer having the first metal oxide transparent conductive film layer / metal film layer / first metal oxide transparent conductive film layer of the present invention as a light-transmitting electrode, due to the microcavity effect, the light intensity in the direction perpendicular to the substrate is greatly improved and strengthened, thereby achieving high efficiency of the device.
[0134] The present application also provides a display device, which includes the above-mentioned organic electroluminescent device. In some optional embodiments, the present application provides a display device, which is a bottom-emitting OLED display device, which includes a matrix-divided light-transmitting electrode and a reflective electrode covering a substrate, and an organic functional material film layer located between the two electrodes. The two electrodes are connected to an external driving circuit. The light-transmitting electrode is the above-mentioned light-transmitting electrode of the present invention, wherein a partial area of the surface of the second metal oxide transparent conductive film layer is covered with an auxiliary electrode film layer material. In particular, the auxiliary electrode film layer material is one of the sandwich structures of Mo, Cr, and Mo / Al / Mo multilayer film combinations. Preferably, the display device has independently controlled light-transmitting electrodes and reflective electrodes with coplanar characteristics for each pixel.
[0135] The display device of the present application is a liquid crystal display device, and the backlight source of the liquid crystal display device is the organic electroluminescent device described in the present application.
[0136] Figure 5 This is a schematic diagram of a top view of a display device based on the present invention. As shown in the figure, the light-transmitting electrode described in the present application is divided into an array arranged in a certain direction, and the reflective electrode is also divided into an array structure arranged in another direction. An organic functional material layer is arranged between the two electrodes, and the intersection of the two different types of array electrodes becomes a pixel point, which generates light under the action of an electric field. Figure 5In the figure, (3) refers to the auxiliary electrode film material that is in contact with the light-transmitting electrode. The use of the auxiliary electrode can greatly reduce the line resistance of the light-transmitting electrode, thereby improving the uniformity of light emission within the surface of the OLED display. Examples of materials commonly used as auxiliary electrodes include metal multilayer film structures such as Mo, Mo / Al / Mo, or single metal film materials such as Cr. The reason for choosing these metal materials as auxiliary electrode materials is, on the one hand, because these materials have good electrical conductivity, and on the other hand, because these metal material films have different etching processes and materials from metal oxide conductive materials, which can realize the patterned preparation of auxiliary electrodes. However, it should be noted that whether an auxiliary electrode is needed depends on the screen size of the OLED display device and the resistivity of the light-transmitting electrode. Not all display devices require auxiliary electrodes to reduce line resistance.
[0137] Figure 6 This is a schematic diagram of the side view structure of a display device based on the present invention. As shown in the figure, the light-transmitting electrode is divided into independent dot matrices to form electrodes of independent pixels, and the TFT (thin film transistor circuit) and the light-transmitting electrode are connected together. Unlike the light-transmitting electrode divided into independent dot matrices, the reflective electrodes of all OLED light-emitting pixels are coplanarly covered on the organic functional material layer. In this characteristic OLED display device, each independent pixel will generate light under the action of the electric field.
[0138] In an embodiment of the present invention, a full-color OLED display may adopt an AM drive or a PM drive mode. When the display adopts an AM drive, a TFT (thin film transistor circuit) control circuit needs to be connected to one of the groups of electrodes to control the light emission of the pixels in a switching manner; when the display adopts a PM drive, the light emission of the pixels of the display is controlled by pulses.
[0139] In addition, it should be noted that the materials used to form each layer described in the present invention can be formed into a film alone and used as a single layer, or can be combined with other materials to form a film and used as a single layer. It can also be a stacked structure between layers formed into films alone, a stacked structure between layers formed into films after combination, or a stacked structure of layers formed into films alone and layers formed into films after combination.
[0140] It should be noted that exemplary embodiments have been disclosed herein, and although specific terms are used therein, these terms are only used and interpreted as general and descriptive meanings, and not for limiting purposes. Unless otherwise specified, features, characteristics and / or elements described in conjunction with a particular embodiment may be used alone or in combination with features, characteristics and / or elements described in conjunction with other embodiments.
[0141] The OLED device of the present invention can be used as a light source for some special purposes, such as a red or yellow light source used in a car taillight, a light source for traffic purposes, etc., and a decorative, warning light source or a light source with lighting effects used in the automotive field or in life. It can also be used to manufacture display devices, which include monochrome display devices or full-color display devices based on color classification; and PM drive display devices or AM drive display devices based on driving form classification. The display device described in this application can be obtained using a preparation method available in the art, and can be used according to the usage method in the art.
[0142] Example
[0143] The following examples are intended to better explain the present invention, but the scope of the present invention is not limited thereto.
[0144] Various materials used in Examples and Comparative Examples are commercially available.
[0145] 1. Preparation of light-transmitting electrodes and their performance testing
[0146] 1. Preparation
[0147] Based on the magnetron sputtering method, the conductive glass containing the light-transmitting electrode shown in Table 1 below was prepared on the surface of a glass substrate with a thickness of 0.5 mm.
[0148] To ensure the reliability of the experiment, in the process of preparing experimental samples, single films of the same material adopt exactly the same preparation process. For example, all ITO transparent conductive film layers are prepared using the same substrate heating method, and the sputtering of metal film layers is completed at room temperature. The proportions of metals included in the metal film layers are all mass ratios.
[0149] 2. Performance Testing
[0150] The prepared conductive glass containing the light-transmitting electrode is tested in a clean room (room temperature, humidity 45%-65%), and the test items include the thin film square resistance and adhesion test of the surface conductive glass.
[0151] 2.1 Determination of thin film sheet resistance
[0152] The thin film square resistance is tested using Suzhou Jingge Electronics ST-2258A four-probe square resistance tester according to the usual method in the field "ST-2258A Multifunctional Digital Four-probe Tester Technical Manual".
[0153] The evaluation criteria for square resistance test are as follows:
[0154] Equivalent: Comparison data ±2Ω / □;
[0155] Reduction: ≥(comparison data -4Ω / □) to <(comparison data -2Ω / □);
[0156] Significantly reduced: <(comparative data -4Ω / □);
[0157] Increase: >(comparison data +2Ω / □);
[0158] Among them, in the present invention, the comparative data is the square resistance of Comparative Example 1 in Table 1, which is 9.0Ω / □.
[0159] 2.2 Determination of adhesion
[0160] Adhesion test is carried out according to ISO 2409 (3rd edition, May 15, 2007) - Test method for measuring adhesion of coatings / platings by tape, where the grid spacing is 2mm*2mm and the special tape for the grid test is 3M600.
[0161] The adhesion test evaluation criteria are as follows:
[0162] ISO Grade 0: The cut edges are completely smooth and there is no peeling on the lattice edges.
[0163] ISO Grade 1: Small flakes peel off at the intersection of the cuts, and the actual damage in the cross-cut area does not exceed 5%.
[0164] ISO Grade 2: There is peeling at the edges and intersections of the cut, with an area of 5%-15%.
[0165] ISO grade 3: The cut edge is peeling off, large pieces are peeling off, and even some grids are peeling off. The peeling area is 15%-35%.
[0166] ISO Grade 4: Large pieces of the cut edge peel off, some grids peel off completely, and the peeled area is 35%-65%.
[0167] ISO level 5: Exceeds the previous level.
[0168] 3. Determination method of film thickness
[0169] Regarding the film thickness measurement method of the organic film layer, the ellipsometer fitting method and the step profiler method can be listed. Among them, the ellipsometer fitting method is an indirect film thickness measurement method and is not the best recommendation. Therefore, in this experiment, the film thickness measurement and definition are carried out according to the method of measuring the film thickness using the step profiler (model D500, manufacturer KLATencor), and are calibrated based on the standard film thickness fixture, and the TF% value of the evaporation equipment is calibrated based on the measured value under the organic film thickness of about 100nm.
[0170] Taking ITO (150 nm) as comparative data, the experimental test data of the light-transmitting electrode are shown in Table 1-1 and Table 1-2.
[0171] Table 1-1
[0172]
[0173]
[0174] It can be seen from the data in Table 1-1 that Examples 1-22 using a light-transmitting electrode including a first metal oxide film layer, a metal film layer, and a second metal oxide film layer have lower square resistance and equivalent or significantly enhanced adhesion performance than Comparative Examples 1-14 using a light-transmitting electrode including a single ITO film layer or a single metal film layer.
[0175] Table 1-2
[0176]
[0177]
[0178] Compared with Examples 12-22, in Examples 1-11, the thickness of the first ITO layer of the light-transmitting electrode is increased from 25nm to 100nm, achieving lower square resistance and better adhesion performance. It can be seen that when the light-transmitting electrodes are all composite structures including a first metal oxide transparent conductive film layer, a metal film layer and a second metal oxide transparent conductive film layer, the thickness of the first and second metal oxide transparent conductive film layers is adjusted to 100nm, and the thickness ratio of the first or second metal oxide transparent conductive film layer to the metal film layer is about 6.67:1. As a result, the square resistance of the light-transmitting electrode is not more than 5Ω / □, and the adhesion is ISO grade 0 or 1. According to the present invention, the thickness of the first metal oxide transparent conductive film layer has a greater influence on the square resistance and adhesion performance of the light-transmitting electrode, and the thickness of the second metal oxide transparent conductive film layer is less sensitive to the square resistance and adhesion performance of the light-transmitting electrode. Therefore, the conductivity and film stability of the light-transmitting electrode can be improved by increasing the thickness of the first metal oxide transparent conductive film layer and adjusting the thickness ratio of the three film layers of the light-transmitting electrode accordingly. Therefore, the thickness of the first metal oxide transparent conductive film layer is preferably greater than 25nm, preferably greater than 50nm, and most preferably 80-120nm. In addition, in the light-transmitting electrode of the present invention, preferably, the sum of the thickness of the first metal oxide transparent conductive film layer and the first metal oxide transparent conductive film layer is preferably greater than 100nm, more preferably greater than 120nm, especially 150-250nm, and most preferably 180-220nm. Within this range, the light-transmitting electrode has better square resistance and adhesion properties.
[0179] It can be seen from Example 12 that the square resistance of the light-transmitting electrode of the ITO (25 nm) / Ag (15 nm) / ITO (100 nm) structure is reduced, but the adhesion performance is slightly worse than that of other examples.
[0180] It can also be seen from the above table that the metal in the metal film layer can be a single metal or a combination of two or three or more metals. The single metals used in this embodiment are Ag and Mo, and the combined metals are Ag+Zn, Ag+Al, Ag+Cu, Al+Cu, Ag+Mg, Ag+Mo, Ag+Pd+Cu, Al+Ca, and Ag+Ca.
[0181] Compared with Examples 1 and 24, in Examples 29-32, the ITO layer of the light-transmitting electrode is adjusted to AZO or AGZO, and excellent conductivity and film stability of the light-transmitting electrode can be obtained;
[0182] Compared with Examples 1 and 23, in Examples 4, 24, and 25, the metal film layer of the light-transmitting electrode is adjusted to a mixed film layer of Ag:Al in different proportions, and excellent conductivity and film stability of the light-transmitting electrode can be obtained;
[0183] The structure of the light-transmitting electrode of the present invention introduces a metal oxide transparent conductive film layer of a specific structure and selects a mixed film layer of different metals in a specific metal type, which is conducive to breaking the lattice structure of a single metal, thereby directly affecting the characteristics and performance of the light-transmitting electrode.
[0184] 2. Preparation and performance testing of OLED
[0185] The molecular structure of the materials used in the device preparation process is shown below:
[0186]
[0187] 1. Preparation of single-layer OLED
[0188] 1.1 Preparation of red OLED
[0189] Example 1
[0190] The organic electroluminescent device was prepared by following the steps below:
[0191] a) using transparent glass as a substrate, coating a metal oxide ITO with a thickness of 100 nm thereon by magnetron sputtering to form a first metal oxide transparent conductive film layer, and then coating a metal Ag with a thickness of 15 nm on the first metal oxide transparent conductive film layer to form a metal film layer; continuing to coat a metal oxide ITO with a thickness of 100 nm thereon by magnetron sputtering to form a second metal oxide transparent conductive film layer, and then ultrasonically cleaning with deionized water, acetone, and ethanol for 15 minutes each, and then treating in a plasma cleaner for 2 minutes, thereby forming an anode layer of a three-layer structure of ITO (100 nm) / Ag (15 nm) / ITO (100 nm), which is a light-transmitting electrode;
[0192] b) On the washed anode layer, hole transport material HT6 and P-type doping material P9 are placed in two evaporation sources respectively, and the vacuum degree is 1.0E -5 Under the pressure of Pa, the evaporation rate of HT6 is controlled to The evaporation rate of P-type dopant material is The hole injection layer is formed by co-evaporation with a thickness of 10 nm;
[0193] c) depositing a hole transport layer on the hole injection layer by vacuum evaporation, wherein the material of the hole transport layer is HT6 and the thickness is 35 nm;
[0194] d) depositing a hole transport auxiliary layer EB-3 on the hole transport layer by vacuum evaporation, with a thickness of 100 nm;
[0195] e) on the hole transport auxiliary layer, a red light-emitting layer material is deposited by vacuum evaporation, wherein the main material is RH-1 and the guest material is RD-1, the mass ratio is 97:3, and the thickness is 40 nm; the peak value of the photoluminescence spectrum of the red light-emitting layer material is 642 nm;
[0196] f) On the light-emitting layer, ET-1 and Liq were evaporated by vacuum evaporation, the mass ratio of ET-1 and Liq was 50:50, and the thickness was 35 nm. This layer served as an electron transport layer;
[0197] g) Yb is deposited on the electron transport layer by vacuum evaporation with a thickness of 1 nm, and this layer is the electron injection layer;
[0198] h) On the electron injection layer, a Mg:Ag electrode layer is vacuum-deposited with a mass ratio of Mg:Ag of 1:9 and a thickness of 80 nm. This layer is the cathode layer.
[0199] Examples 1-1 to 1-5: The steps of Example 1 were repeated, except that the thickness of the first metal oxide transparent conductive film layer (ITO layer) in step a) was changed.
[0200] Example 2: The steps of Example 1 are repeated, except that the material Ag of the metal film layer in step a) is replaced by Mo.
[0201] Examples 2-1 to 2-5: The steps of Example 2 were repeated, except that the thickness of the first metal oxide transparent conductive film layer (ITO layer) in step a) was changed.
[0202] Example 3: The steps of Example 1 are repeated, except that the material Ag of the metal film layer in step a) is replaced by a Ag:Zn composite metal material;
[0203] Examples 3-1 to 3-2: The steps of Example 3 were repeated, except that the metal mass ratio of the metal film layer material in step a) was changed.
[0204] Example 3-3: The steps of Example 3 are repeated, except that the thickness of the first metal oxide transparent conductive thin film layer in step a) is changed.
[0205] Example 4: The steps of Example 1 are repeated, except that the material Ag of the metal film layer in step a) is replaced by a Ag:Al combined metal material.
[0206] Examples 4-1 to 4-4, 4-7: The steps of Example 4 were repeated, except that the thickness of the first metal oxide transparent conductive film layer in step a) was changed.
[0207] Examples 4-5 to 4-6: The steps of Example 4 were repeated, except that the metal mass ratio of the metal film layer material in step a) was changed.
[0208] Example 5: The steps of Example 1 are repeated, except that the material Ag of the metal film layer in step a) is replaced by an Al:Cu composite metal material.
[0209] Examples 5-1 to 5-4, 5-7: The steps of Example 5 were repeated, except that the thickness of the first metal oxide transparent conductive film layer in step a) was changed.
[0210] Examples 5-5 to 5-6: The steps of Example 5 were repeated, except that the metal mass ratio of the metal film layer material in step a) was changed.
[0211] Example 6: The steps of Example 1 are repeated, except that the material Ag of the metal film layer in step a) is replaced by a Ag:Mg composite metal material.
[0212] Examples 6-1 to 6-2: The steps of Example 6 were repeated, except that the metal mass ratio of the metal film layer material in step a) was changed.
[0213] Example 6-3: The steps of Example 6 are repeated, except that the thickness of the first metal oxide transparent conductive thin film layer in step a) is changed.
[0214] Example 7: The steps of Example 1 are repeated, except that the material Ag of the metal film layer in step a) is replaced by a Ag:Cu composite metal material.
[0215] Examples 7-1 to 7-4, 7-7: The steps of Example 7 were repeated, except that the thickness of the first metal oxide transparent conductive film layer in step a) was changed.
[0216] Examples 7-5 to 7-6: The steps of Example 7 were repeated, except that the metal mass ratio of the metal film layer material in step a) was changed.
[0217] Example 8: The steps of Example 1 are repeated, except that the material Ag of the metal film layer in step a) is replaced by a Ag:Mo combined metal material.
[0218] Examples 8-1 to 8-4, 8-7: The steps of Example 8 were repeated, except that the thickness of the first metal oxide transparent conductive film layer in step a) was changed.
[0219] Examples 8-5 to 8-6: The steps of Example 8 were repeated, except that the metal mass ratio of the metal film layer material in step a) was changed.
[0220] Example 9: The steps of Example 1 are repeated, except that the material Ag of the metal film layer in step a) is replaced by a combined metal material of Ag:Pd:Cu with a weight ratio of 98:1:1.
[0221] Example 9-1: The steps of Example 9 are repeated, except that the thickness of the first metal oxide transparent conductive film layer in step a) is changed.
[0222] Example 10: The steps of Example 1 are repeated, except that the material Ag of the metal film layer in step a) is replaced by a Ag:Ca combined metal material.
[0223] Example 11: The steps of Example 1 are repeated, except that the material Ag of the metal film layer in step a) is replaced by an Al:Ca combined metal material.
[0224] Example 12: The steps of Example 9 are repeated, except that the first metal oxide transparent conductive film layer (ITO layer) in step a) is replaced by AZO.
[0225] Comparative Example 1
[0226] The steps of Example 1 are repeated, except that there is no metal film layer in the anode layer, and the specific operation of step a) is as follows:
[0227] a) using transparent glass as a substrate, coating ITO with a thickness of 150 nm as an anode layer thereon by magnetron sputtering, ultrasonically cleaning with deionized water, acetone, and ethanol for 15 minutes each, and then treating in a plasma cleaner for 2 minutes; thereby forming an anode layer of a single-layer structure of ITO (150 nm).
[0228] The specific structures of the anode layers and device performances of the above-mentioned embodiments and comparative examples are shown in Table 2.
[0229] 1.2 Preparation of blue OLED
[0230] Embodiment 13
[0231] The steps of Example 1 were repeated, except that the hole transport auxiliary layer EB-3 in step d) was replaced by EB-1 with a thickness of 10 nm; the main material RH-1 of the light-emitting layer in step e) was replaced by BH-1, the guest material RD-1 was replaced by BD-1, and the mass ratio of BH-1 to BD-1 was 97:3, with a thickness of 20 nm; the peak value of the photoluminescence spectrum of the blue light-emitting layer material was 460 nm.
[0232] Examples 14-17: The steps of Example 13 were repeated, except that the metal film layer material in step a) was changed, and the anode layer structure was as shown in Table 2.
[0233] Comparative Example 2
[0234] The steps of Example 13 were repeated, except that there was no metal film layer in the anode layer, and the specific operation of step a) was as follows:
[0235] a) using transparent glass as a substrate, coating ITO with a thickness of 150 nm as an anode layer thereon by magnetron sputtering, ultrasonically cleaning with deionized water, acetone, and ethanol for 15 minutes each, and then treating in a plasma cleaner for 2 minutes; thereby forming an anode layer of a single-layer structure of ITO (150 nm).
[0236] Examples 18-22: The steps of Example 13 are repeated, except that the ITO thickness and / or the metal film layer material in step a) are changed.
[0237] The specific structures of the anode layers and device performances of the above comparative examples and embodiments are shown in Table 2.
[0238] 1.3 Preparation of green OLED
[0239] Embodiment 23
[0240] The steps of Example 1 were repeated, except that the hole transport auxiliary layer EB-3 in step d) was replaced by EB-2 with a thickness of 40 nm; the main material RH-1 of the light-emitting layer in step e) was replaced by GH-1 and GH-2, the guest material RD-1 was replaced by GD-1, and the mass ratio of GH-1, GH-2 and GD-1 was 47:47:6, with a thickness of 40 nm; the peak photoluminescence spectrum of the green light-emitting layer material was 530 nm.
[0241] Examples 24-27: The steps of Example 23 were repeated, except that the metal film layer material in step a) was changed, and the anode layer structure was as shown in Table 2.
[0242] Comparative Example 3
[0243] The steps of Example 23 were repeated, except that there was no metal film layer in the anode layer, and the specific operation of step a) was as follows:
[0244] a) using transparent glass as a substrate, coating ITO with a thickness of 150 nm as an anode layer thereon by magnetron sputtering, ultrasonically cleaning with deionized water, acetone, and ethanol for 15 minutes each, and then treating in a plasma cleaner for 2 minutes; thereby forming an anode layer of a single-layer structure of ITO (150 nm).
[0245] Examples 28-32: The steps of Example 23 are repeated, except that the ITO thickness and / or the metal film layer material in step a) are changed.
[0246] The specific structures of the anode layers and device performances of the above comparative examples and embodiments are shown in Table 2.
[0247] 1.4 Yellow OLED Preparation
[0248] Embodiment 33
[0249] The steps of Example 1 were repeated, except that the hole transport auxiliary layer EB-3 in step d) was replaced by EB-2 with a thickness of 60 nm; the main material RH-1 of the light-emitting layer in step e) was replaced by GH-1 and GH-2, the guest material RD-1 was replaced by YD-1, and the mass ratio of GH-1, GH-2 and YD-1 was 47:47:6, with a thickness of 40 nm; the peak value of the photoluminescence spectrum of the yellow light-emitting layer material was 568 nm.
[0250] Examples 34-37: The steps of Example 33 are repeated, except that the metal film layer material in step a) is changed, and the anode layer structure is as shown in Table 2.
[0251] Comparative Example 4
[0252] The steps of Example 33 were repeated, except that there was no metal film layer in the anode layer, and the specific operation of step a) was as follows:
[0253] a) using transparent glass as a substrate, coating ITO with a thickness of 150 nm as an anode layer thereon by magnetron sputtering, ultrasonically cleaning with deionized water, acetone, and ethanol for 15 minutes each, and then treating in a plasma cleaner for 2 minutes; thereby forming an anode layer of a single-layer structure of ITO (150 nm).
[0254] Examples 38-42:
[0255] The steps of Example 33 are repeated, except that the ITO thickness and / or the metal film layer material in step a) are changed.
[0256] The specific structures of the anode layers and device performances of the above comparative examples and embodiments are shown in Table 2.
[0257] 1.5 Amber OLED Preparation
[0258] Embodiment 43
[0259] The steps of Example 1 were repeated, except that the hole transport auxiliary layer EB-3 in step d) was replaced by EB-2 with a thickness of 60 nm; the host material RH-1 of the light-emitting layer in step e) was replaced by GH-1 and GH-2, the guest material RD-1 was replaced by AD-1, and the mass ratio of GH-1, GH-2 and AD-1 was 47:47:6, with a thickness of 40 nm; the peak photoluminescence spectrum of the amber light-emitting layer material was 580 nm.
[0260] Examples 44-47: The steps of Example 43 were repeated, except that the metal film layer material in step a) was changed, and the anode layer structure was as shown in Table 2.
[0261] Comparative Example 5
[0262] The steps of Example 43 were repeated, except that there was no metal film layer in the anode layer, and the specific operation of step a) was as follows:
[0263] a) using transparent glass as a substrate, coating ITO with a thickness of 150 nm as an anode layer thereon by magnetron sputtering, ultrasonically cleaning with deionized water, acetone, and ethanol for 15 minutes each, and then treating in a plasma cleaner for 2 minutes; thereby forming an anode layer of a single-layer structure of ITO (150 nm).
[0264] Examples 48-52:
[0265] The steps of Example 43 are repeated, except that the ITO thickness and / or the metal film layer material in step a) are changed.
[0266] The specific structures of the anode layers of the above comparative examples and embodiments are shown in Table 2.
[0267] The preparation process parameters and device performance of the OLEDs of the above embodiments and comparative examples are shown in Table 2.
[0268] Select Examples 1 / 2 / 3 / 4 / 5 / 6 / 7 / 8 / 9 / 10 / 11 to test the performance of the device at a 40° angle, use the Example number as the horizontal axis, and use the ratio of the light intensity in the direction perpendicular to the substrate to the light intensity in the direction at a 40° angle to the substrate as the vertical axis, and draw a graph as shown below: Figure 8 shown.
[0269] Table 2
[0270]
[0271]
[0272]
[0273]
[0274]
[0275]
[0276] It can be seen from the data in Table 2 that for red, blue, green, yellow or amber OLED devices, among the light-emitting devices of the same color, the devices of the embodiments of the present invention have significantly improved current efficiency and service life compared with the comparative examples.
[0277] In addition, it can be seen from Table 2 that when using a light-transmitting electrode (anode layer) composed of a first metal oxide transparent conductive film layer, a metal film layer, and a second metal oxide transparent conductive film layer, under the same other conditions, an OLED device obtained by using a metal film layer composed of Mo has better current efficiency and LT95 life than a metal film layer composed of Ag; an OLED device obtained by using a metal film layer composed of a combination of metals can achieve better current efficiency and LT95 life than a film layer composed of a single metal. The preferred combination of metals is Ag+Al, Ag+Cu, Ag+Mo, Ag+Pd+Cu, and Ag+Pd+Cu is particularly preferred. In addition, the ratio between the metals in the combination of metals also affects the OLED device.
[0278] It can also be seen from Table 2 that the thickness of the first metal oxide transparent conductive film layer has a great influence on the current efficiency and LT95 life. Therefore, the thickness of the first metal oxide transparent conductive film layer is controlled within a suitable thickness range according to the material of the metal film layer, for example, in the case of Ag, it is controlled within the range of 80-120nm, preferably 90-110nm, and most preferably 100nm. In the case of combined metal or Mo, a thinner and wider range of the first metal oxide transparent conductive film layer can be used, for example, 10-150nm, preferably 20-120nm, and more preferably 25-110nm; and, the increase in the thickness of the first metal oxide transparent conductive film layer will be more conducive to achieving the current efficiency and life of the OLED device. It can be seen from Example 12 that the first metal oxide transparent conductive film layer using AZO can achieve better device performance than using ITO. The type and thickness of the first metal oxide transparent conductive film layer and the second metal oxide transparent conductive film layer can be the same or different.
[0279] from Figure 8 It can be seen that the light intensity of the device of the present invention in the direction perpendicular to the substrate is significantly improved, and the ratio of the light intensity to the light intensity in the direction at an angle of 40 degrees to the substrate is greater than 1.5 times.
[0280] In the embodiments, the thickness and type of the second metal oxide transparent conductive film layer are not changed, because it is found in practice that the change of the thickness of this layer is not so sensitive to the performance of the OLED device. Nevertheless, the sum of the thicknesses of the first metal oxide transparent conductive film layer and the second metal oxide transparent conductive film layer is important. To achieve a good OLED device, the sum is preferably greater than 100 nm, preferably 110-250 nm, especially 120-240 nm, more preferably 150-220 nm, and most preferably 180-210 nm.
[0281] 2. Preparation of stacked OLEDs
[0282] 2.1 Dual-color stacked OLED - blue, red
[0283] Embodiment 55
[0284] The stacked organic electroluminescent device was prepared according to the following steps:
[0285] a) using transparent glass as a substrate, coating a metal oxide ITO with a thickness of 100 nm thereon by magnetron sputtering to form a first metal oxide transparent conductive film layer; then coating a metal Ag with a thickness of 15 nm on the first metal oxide transparent conductive film layer to form a metal film layer; continuing to coat a metal oxide ITO with a thickness of 100 nm thereon by magnetron sputtering to form a second metal oxide transparent conductive film layer, then ultrasonically cleaning with deionized water, acetone, and ethanol for 15 minutes each, and then treating in a plasma cleaner for 2 minutes; thereby obtaining an anode layer of an ITO (100 nm) / Ag (15 nm) / ITO (100 nm) structure;
[0286] b) On the washed anode layer, hole transport material HT6 and P-type doping material P9 are placed in two evaporation sources respectively, and the vacuum degree is 1.0E -5 Under the pressure of Pa, the evaporation rate of HT6 is controlled to The evaporation rate of P-type dopant material is The hole injection layer is formed by co-evaporation with a thickness of 10 nm;
[0287] c) depositing a hole transport layer on the hole injection layer by vacuum evaporation, wherein the material of the hole transport layer is HT6 and the thickness is 35 nm;
[0288] d) depositing a hole transport auxiliary layer EB-1 on the hole transport layer by vacuum evaporation, with a thickness of 5 nm;
[0289] e) On the hole transport auxiliary layer, the light-emitting layer material is deposited by vacuum evaporation, the main material is BH-1, the guest material is BD-1, the mass ratio is 97:3, and the thickness is 20 nm;
[0290] f) On the light-emitting layer, ET-1 and Liq were evaporated by vacuum evaporation, the mass ratio of ET-1 and Liq was 50:50, and the thickness was 35 nm. This layer served as an electron transport layer;
[0291] g) On the electron transport layer, ET-2 and Li are evaporated by vacuum evaporation, the mass ratio of ET-2 to Li is 97:3, and the thickness is 10 nm. This layer serves as a charge generation layer;
[0292] h) On the charge generation layer, at a vacuum degree of 1.0E -5Under the pressure of Pa, the evaporation rate of HT6 is controlled to The evaporation rate of P-type dopant material is The hole injection layer is formed by co-evaporation with a thickness of 10 nm;
[0293] i) on the hole injection layer, a hole transport layer is deposited by vacuum evaporation, the hole transport layer material is HT6, and the thickness is 20 nm;
[0294] j) depositing a hole transport auxiliary layer EB-3 on the hole transport layer by vacuum evaporation, with a thickness of 5 nm;
[0295] k) on the hole transport auxiliary layer, the light-emitting layer material is deposited by vacuum evaporation, the main material is RH-1, the guest material is RD-1, the mass ratio of RH-1 to RD-1 is 97:3, and the thickness is 40 nm;
[0296] l) On the light-emitting layer, ET-1 and Liq were evaporated by vacuum evaporation, the mass ratio of ET-1 and Liq was 50:50, and the thickness was 40 nm. This layer served as an electron transport layer;
[0297] m) Yb is deposited on the electron transport layer by vacuum evaporation with a thickness of 1 nm, and this layer is the electron injection layer;
[0298] n) On the electron injection layer, a Ag electrode layer with a thickness of 150 nm is vacuum-deposited, which is the cathode layer.
[0299] Examples 53-54: The steps of Example 55 are repeated, except that the ITO thickness and / or the metal film layer material in step a) are changed.
[0300] Examples 56-63
[0301] The steps of Example 55 were repeated, except that the material for forming the metal film layer in step a) was changed as shown in Table 3;
[0302] Comparative Example - Double 1
[0303] The steps of Example 55 were repeated, except that the specific operation of step a) was as follows:
[0304] a) using transparent glass as a substrate, coating ITO with a thickness of 150 nm as an anode layer thereon by magnetron sputtering, ultrasonically cleaning with deionized water, acetone, and ethanol for 15 minutes each, and then treating in a plasma cleaner for 2 minutes;
[0305] The specific structures of the anode layers and device performances of the above-mentioned embodiments and comparative examples are shown in Table 3.
[0306] 2.2 Monochrome stacked OLED - red, red
[0307] Embodiment 66
[0308] The steps of Example 55 are repeated, except that in step c), the thickness of the hole transport layer HT6 is changed to 135 nm; in step d), the hole transport auxiliary layer EB-1 is replaced by EB-3 with a thickness of 5 nm; in step e), the main material is RH-1, the guest material is RD-1, the mass ratio of RH-1 to RD-1 is 97:3, and the thickness is 40 nm; in step i), the thickness of the hole transport layer HT6 is changed to 70 nm.
[0309] Examples 64-65: The steps of Example 66 are repeated, except that the ITO thickness and the metal film layer material in step a) are changed.
[0310] Examples 67-74: The steps of Example 66 are repeated, except that the material for forming the metal film layer in step a) is changed as shown in Table 3.
[0311] Comparative Example - Double 2
[0312] The steps of Example 66 were repeated, except that the ITO thickness and the metal film layer material in step a) were changed, and the specific structure of the anode layer was shown in Table 3. The specific operation of step a) is as follows:
[0313] a) A transparent glass substrate was used as a substrate, and an ITO layer with a thickness of 150 nm was coated thereon as an anode layer by magnetron sputtering, and the substrate was ultrasonically cleaned with deionized water, acetone, and ethanol for 15 minutes each, and then treated in a plasma cleaner for 2 minutes.
[0314] The specific structures of the anode layers and device performances of the above embodiments and comparative examples are shown in Table 3.
[0315] 2.3 Monochrome stacked OLED - yellow, yellow
[0316] Embodiment 76
[0317] The steps of Example 55 were repeated, except that in step c), the thickness of the hole transport layer HT6 was changed to 75 nm;
[0318] In step d), the hole transport auxiliary layer EB-1 is replaced by EB-2 with a thickness of 5 nm; in step e), the main materials are GH-1 and GH-2, the guest material is YD-1, the mass ratio of GH-1, GH-2 and YD-1 is 47:47:6, and the thickness is 40 nm; in step i), the thickness of the hole transport layer HT6 is changed to 70 nm; in step j), the hole transport auxiliary layer EB-3 is replaced by EB-2 with a thickness of 5 nm; in step k), the main materials are GH-1 and GH-2, the guest material is YD-1, the mass ratio of GH-1, GH-2 and YD-1 is 47:47:6, and the thickness is 40 nm.
[0319] Example 75: Repeat the steps of Example 76, except that the ITO thickness and the metal film layer material in step a) are changed.
[0320] Example 77: Repeat the steps of Example 76, except that the material for forming the metal film layer in step a) is changed as shown in Table 3.
[0321] Comparative Example - Double 3
[0322] The steps of Example 76 were repeated, except that the specific operation of step a) was as follows:
[0323] b) A transparent glass substrate was used as a substrate, and an ITO layer with a thickness of 150 nm was coated thereon as an anode layer by magnetron sputtering, and the substrate was ultrasonically cleaned with deionized water, acetone, and ethanol for 15 minutes each, and then treated in a plasma cleaner for 2 minutes.
[0324] The specific structures of the anode layers and device performances of the above embodiments and comparative examples are shown in Table 3.
[0325] 2.4 Monochrome stacked OLED - amber, amber
[0326] Embodiment 79
[0327] The steps of Example 55 are repeated, except that in step c), the thickness of the hole transport layer HT6 is changed to 75 nm; in step d), the hole transport auxiliary layer EB-1 is replaced by EB-2 with a thickness of 5 nm; in step e), the main materials are GH-1 and GH-2, the guest material is AD-1, the mass ratio of GH-1, GH-2 and AD-1 is 47:47:6, and the thickness is 40 nm; in step i), the thickness of the hole transport layer HT6 is changed to 70 nm; in step j), the hole transport auxiliary layer EB-3 is replaced by EB-2 with a thickness of 5 nm; in step k), the main materials are GH-1 and GH-2, the guest material is AD-1, the mass ratio of GH-1, GH-2 and AD-1 is 47:47:6, and the thickness is 40 nm.
[0328] Embodiment 78:
[0329] Repeat the steps of Example 79, except that the thickness of the ITO and the metal film layer material in step a) is changed.
[0330] Embodiment 80:
[0331] The steps of Example 79 were repeated, except that the material for forming the metal film layer in step a) was changed as shown in Table 3.
[0332] Comparative Example - Double 4
[0333] The steps of Example 79 were repeated, except that the specific operation of step a) was as follows:
[0334] c) A transparent glass substrate was used as a substrate, and an ITO layer with a thickness of 150 nm was coated thereon as an anode layer by magnetron sputtering, and the substrate was ultrasonically cleaned with deionized water, acetone, and ethanol for 15 minutes each, and then treated in a plasma cleaner for 2 minutes.
[0335] The preparation process parameters and device performance of the stacked OLED of the above-mentioned embodiment and comparative example are shown in Table 3.
[0336]
[0337]
[0338] In Tables 2 and 3, the performance tests of the OLED devices were conducted as follows: the current efficiency and color coordinates were tested using an IVL (current-voltage-luminance) test system (Suzhou Fushida Scientific Instrument Co., Ltd.) at a current density of 10 mA / cm 2 ; The life test system is the EA S-62C OLED device life tester of Japan System Technology Co., Ltd.; LT95 refers to the 2 The time it takes for the device brightness to decay to 95% under the condition of .
[0339] It can be seen from the data in Table 3 that for the stacked OLED device, the current efficiency and service life of the device in the embodiment of the present invention are improved compared with the comparative example. In addition, it can also be seen from Table 3 that when the metal layer material of the metal film layer and the thickness of the first metal oxide transparent conductive film layer are changed, the current efficiency and service life of the stacked OLED device show a trend similar to that of the single-layer OLED device and the current effect is similar to that of the single-layer structure device. This shows that the light-transmitting electrode described in the present application is also applicable to stacked OLED devices, especially double-layer OLED devices, especially monochrome stacked OLED devices.
[0340] In addition, whether it is a single-layer OLED device or a stacked OLED device, it is preferred that the thickness of the second metal oxide transparent conductive film layer and the organic functional material layer satisfy the relationship described above. When the above relationship is satisfied, both the single-layer OLED device and the stacked OLED device can exhibit strong microcavity characteristics and achieve good current efficiency and service life. As shown in Examples 1-80, the specific results are shown in Tables 2 and 3.
[0341] Examples 4-8 to 4-10: The steps of Example 4 were repeated, except that the ratio of Ag:Al of the metal film layer material in step a) was changed.
[0342] Examples 4-11 to 4-12: The steps of Example 4 are repeated, except that the metal oxide transparent conductive film layer material and the ratio of Ag:Al in the metal film layer material in step a) are changed.
[0343] Examples 81-85: The steps of Example 66 are repeated, except that the type of the metal film layer material in step a) is changed;
[0344] Examples 86-87: The steps of Example 66 are repeated, except that the types of materials of the metal oxide transparent conductive thin film layer and the metal film layer in step a) are changed;
[0345] The structures of Examples 4-8 to 4-12 and Examples 81-87 are shown in Table 4 below;
[0346] Table 4
[0347]
[0348]
[0349] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. An organic electroluminescent device, comprising, from bottom to top: Substrate, light-transmitting electrode, organic functional material layer, reflective electrode; characterized in that the light-transmitting electrode comprises: A first metal oxide transparent conductive film layer directly covers the substrate; A metal film layer directly covering the first metal oxide transparent conductive film layer; The second metal oxide transparent conductive film layer directly covers the metal film layer.
2. The organic electroluminescent device according to claim 1, characterized in that: The sum of the thicknesses of the first metal oxide transparent conductive film layer and the second metal oxide transparent conductive film layer is greater than 100 nm; optionally, the thicknesses of the first metal oxide transparent conductive film layer and the second metal oxide transparent conductive film layer are 10-150 nm, preferably 20-120 nm; optionally, the thickness of the metal film layer is 5-30 nm, preferably 10-20 nm.
3. The organic electroluminescent device according to claim 1 or 2, characterized in that: The metal film layer material is selected from a combination of one or more metals selected from Ag, Al, Cu, Ca, Cr, Pd, Mg, Zn or Mo; optionally, the metal film layer material includes or is selected from two or more metals selected from Ag, Al, Cu, Ca, Cr, Pd, Mg, Zn or Mo.
4. The organic electroluminescent device according to claim 1, characterized in that: The metal film layer is a single metal material or a single-layer thin film material mixed with multiple metal materials, or a multi-layer superposition structure of multiple metal material film layers, and the metal material includes one, two or three of Ag, Al, Cu, Ca, Cr, Pd, Mg, Zn or Mo.
5. The organic electroluminescent device according to claim 3, characterized in that: The metal film layer material includes or is selected from the following metal combinations: 1) a combination of two or more of the first metals, wherein the first metal is Ag, Al, Cu, Ca, Cr or Mo; or 2) a combination of any one or more of the first metals and a second metal, wherein the second metal is Pd, Mg or Zn.
6. The organic electroluminescent device according to claim 5, characterized in that: The metal film layer material includes or is selected from a combination of two metals in the first metal, including a combination of Al and Cu, a combination of Al and Mo, a combination of Al and Ca, a combination of Al and Cr, a combination of Ag and Al, a combination of Ag and Cu, a combination of Ag and Mo, a combination of Ag and Ca, a combination of Ag and Cr, a combination of Cu and Cr, and a combination of Cu and Mo; optionally, the mass ratio of the two metals in the above metal combination is 2:3 to 10:1, preferably 1:1 to 9:1; in particular, in the combination of Ag and Al, Ag and Cu, Ag and Mo, Ag and Ca, and Ag and Cr, the mass ratio of Ag to Al, Cu, Mo, Ca or Cr is 2:3 to 10:1, preferably 1:1 to 9:1; in the combination of Cu and Cr, and Cu and Mo, the mass ratio of Cu to Cr or Mo is 2:3 to 10:1, preferably 1:1 to 9:
1. Alternatively, the metal film layer material includes or is selected from a combination of a first metal and a second metal, including a combination of Ag and Zn, a combination of Ag and Mg, a combination of Ag, Pd and Cu, a combination of Cu and Zn, a combination of Cu and Mg, a combination of Ag and Zn, and a three-metal combination of Ag, Pd and Cu, wherein the total mass ratio of the first metal to metal materials other than the first metal is 1:1 to 99:
1.
7. The organic electroluminescent device according to claim 1, characterized in that: The metal film layer material is a single metal, which is selected from one of Ag, Al, Cu, Ca, Cr, Pd, Mg, Zn or Mo, and the thickness of the first metal oxide transparent conductive film layer is 50-150nm, preferably 60-120nm.
8. The organic electroluminescent device according to claim 1, characterized in that: The metal film layer is a multi-layer stacking structure, wherein the material of each layer in the multi-layer stacking structure includes or is selected from one or more metals selected from Ag, Al, Cu, Ca, Cr, Pd, Mg, Zn or Mo.
9. The organic electroluminescent device according to any one of claims 1 to 8, characterized in that: The thicknesses of the second metal oxide transparent conductive film layer and the organic functional material layer satisfy the following relationship: Y=(0.6477X-88.3nm)±15nm, Wherein Y is the sum of the thickness of the second metal oxide transparent conductive film layer and the total film thickness of the organic functional material layer sandwiched between the second metal oxide transparent conductive film layer and the reflective electrode; X is the peak value of the photoluminescence spectrum of the light-emitting layer material of the organic electroluminescent device; Preferably, the organic electroluminescent device is a single-layer or stacked-layer organic electroluminescent device.
10. The organic electroluminescent device according to any one of claims 1 to 8, characterized in that: The thicknesses of the second metal oxide transparent conductive film layer and the organic functional material layer satisfy the following relationship: Y=(0.9247X-85.9)±15nm, Wherein Y is the sum of the thickness of the second metal oxide transparent conductive film layer and the total film thickness of the organic functional material layer sandwiched between the second metal oxide transparent conductive film layer and the reflective electrode; X is the peak value of the photoluminescence spectrum of the light-emitting layer material of the organic electroluminescent device; Preferably, the organic electroluminescent device is a stacked organic electroluminescent device.
11. The organic electroluminescent device according to any one of claims 1 to 10, characterized in that: The materials of the first metal oxide transparent conductive film layer and the second metal oxide transparent conductive film layer are independently selected from one or more of indium tin oxide ITO, indium zinc oxide IZO, aluminum zinc oxide AZO, gallium zinc oxide GZO, aluminum gallium zinc oxide AGZO, and fluorine-doped tin oxide FTO.
12. The organic electroluminescent device according to any one of claims 1 to 11, characterized in that: The thickness ratio of the first metal oxide transparent conductive film layer to the metal film layer is 2.5:1 to 12.5:
1.
13. The organic electroluminescent device according to any one of claims 1 to 12, characterized in that: The reflective electrode includes at least one or more metals selected from Ag, Al, Ca, and Mg.
14. The organic electroluminescent device according to any one of claims 1 to 13, characterized in that: When the device is used as a surface light source for testing, the ratio of the light intensity in the direction perpendicular to the substrate to the light intensity in the direction at an angle of 40 degrees to the substrate, among the light emitted by the organic electroluminescent device in all directions, is greater than 1.5 times, preferably greater than 2 times.
15. The organic electroluminescent device according to any one of claims 1 to 14, characterized in that: The organic functional material layer comprises a hole transport region, a light emitting region and an electron transport region, the hole transport region comprises a hole injection layer and a hole transport layer, the hole injection layer is selected from a host material represented by the general formula (I-1) or the general formula (I-2), and a doping material represented by the general formula (I-3), or is selected from a single film layer material represented by the general formula (I-3): wherein Ar1-Ar4 are independently selected from substituted or unsubstituted C6-C 60 aryl or substituted or unsubstituted 5-60 membered heteroaryl; L1, L2 are phenylene or naphthylene; The substituents for the above groups are selected from: C1-C 10 Alkyl, C3-C 10 Cycloalkyl, C6-C 60 aryl, 5-60 membered heteroaryl; Preferably, the host materials represented by general formula (I-1) and general formula (I-2) are selected from the following specific compounds: Preferably, the doping material of general formula (I-3) is selected from the following compounds:
16. The organic electroluminescent device according to any one of claims 1 to 13, characterized in that: The organic functional material layer includes two or more light-emitting units and a charge generation layer, wherein the light-emitting units each independently include a hole transport region, a light-emitting region, and an electron transport region; the charge generation layer is located between two adjacent light-emitting units, especially the charge generation layer includes a compound with a phenanthroline structure, and the thickness of the charge generation layer is 5 to 15 nm.
17. The organic electroluminescent device according to claim 16, characterized in that: The charge generation layer is further doped with a metal material, wherein the metal material is one or more of Li, Ca, Ag, Cs or Yb; the doping ratio of the metal material is 0.1-3.1 wt %, based on the weight of the compound containing a phenanthroline structure.
18. The organic electroluminescent device according to claim 16, characterized in that: The organic functional material layer includes two light-emitting units, wherein the light-emitting region of one light-emitting unit includes a blue light-emitting material, and the light-emitting region of the other light-emitting unit includes a red light-emitting material.
19. A display device comprising the organic electroluminescent device according to any one of claims 1 to 18.
20. The display device according to claim 19 comprises a light-transmitting electrode and a reflective electrode which are covered on a substrate and divided into a matrix, and an organic functional material layer located between the light-transmitting electrode and the reflective electrode, wherein the light-transmitting electrode and the reflective electrode are both connected to an external driving circuit, and the light-transmitting electrode is the light-transmitting electrode in the organic electroluminescent device according to any one of claims 1 to 17, wherein a partial area on the surface of the second metal oxide transparent conductive film layer is covered with an auxiliary electrode film layer material; in particular, the auxiliary electrode film layer material is one of the sandwich structures of Mo, Cr, and Mo / Al / Mo multilayer film combinations; preferably, the display device has independently controlled light-transmitting electrodes and reflective electrodes with coplanar characteristics for each pixel.
21. The display device according to claim 19, characterized in that: The display device is a liquid crystal display device, and the backlight source of the liquid crystal display device is the organic electroluminescent device according to any one of claims 1 to 18.
Citation Information
Patent Citations
Adjustable cane with enhanced grasping mechanism, magnetic pickup, hanging tip and self-standing base
US20080128009A1
Novel Materials for Organic Electroluminescent Devices
US20080193797A1
Novel Materials for Organic Electroluminescent Devices
US20080220285A1
OLED device with certain fluoranthene host
US20090110957A1
Organic electroluminescence device
US20100295444A1